Catalyst for dehydrogenation reaction
By adopting a combined structure of perovskite oxide and composite oxide in the catalyst, the problem of degradation of the heat resistance and activity of the catalyst in the methane oxidation coupling reaction is solved, and the efficient stability and activity of the catalyst are improved.
Patent Information
- Application Number
- CN202380057416.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The methane oxidation coupling reaction causes a sharp increase in the catalyst temperature due to exothermic heat, resulting in a decrease in the catalyst heat resistance and activity, and there is still room for improvement in the heat resistance and catalytic activity of the catalyst in the prior art.
Perovskite-type oxide composed of the general formula (A1-xA’x) (Zr1-y-zByB’z)O3-δ is used as the main phase, and composite oxides such as AB’2O4, A2B’2O5, A3B’4O9 are added as the catalyst for the secondary phase. By optimizing the element composition and structural design, the heat resistance and catalytic activity of the catalyst are improved.
The heat resistance and catalytic activity of the catalyst are significantly improved, and the stable performance can be maintained under high temperature conditions, reducing the deactivation of the catalyst.
Smart Images

Figure CN119630483A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to catalysts for dehydrogenation reactions. Background Art
[0002] In the past, various catalysts have been proposed as catalysts for the oxidative coupling of methane for producing hydrocarbons having a carbon number of 2 or more, such as ethylene, from methane (e.g., Patent Documents 1 and 2 and Non-Patent Document 1). Patent Document 1 discloses an alkali metal halide-supported samarium oxide catalyst as a methane oxidative coupling catalyst, and shows that such a catalyst can withstand a durability test under a temperature condition of 750°C.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 08-010620
[0006] Patent Document 2: Japanese Patent Application Laid-Open No. 61-282323
[0007] Non-patent literature
[0008] Non-patent literature 1: Seoyeon Lim, Jae-Wook Choi, Dong Jin Suh, Kwang Ho Song, Hyung Chul Ham, Jeong-Myeong Ha, "Combined experimental and density functional theory (DFT) studies on the catalyst design for the oxidative coupling ofmethane", Journal of Catalysis, Volume 375, July 2019, Pages478-492 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] The methane oxidative coupling reaction is an exothermic reaction, so there is a possibility that the catalytic temperature rises sharply as the reaction proceeds. For example, when a hydrocarbon manufacturing facility that utilizes the methane oxidative coupling reaction is industrialized (large-scaled), there is a possibility that the temperature of the catalyst rises even more due to the rapid progress of the exothermic reaction. Moreover, when the catalytic temperature rises significantly in this way, there is a possibility of adverse conditions such as deactivation of the methane oxidative coupling catalyst. Therefore, further improvement in the heat resistance of the methane oxidative coupling catalyst is desired. The methane oxidative coupling reaction is a type of dehydrogenation reaction, but it is not easy to be limited to the methane oxidative coupling reaction. The dehydrogenation reaction is generally an exothermic reaction, and there is a possibility that the catalytic temperature rises sharply as the reaction proceeds. Therefore, the above-mentioned issues involving the heat resistance of the catalyst are common issues in catalysts for dehydrogenation reactions.
[0011] However, according to the prior art such as Patent Documents 1, 2 and Non-Patent Document 1, there is still room for improvement in the technology for improving the heat resistance of the catalyst for dehydrogenation reaction. In addition, according to the prior art such as Patent Documents 1, 2 and Non-Patent Document 1, there is still room for improvement in the technology for improving the catalytic activity of the catalyst for dehydrogenation reaction. Furthermore, according to the prior art such as Patent Documents 1, 2 and Non-Patent Document 1, there is still room for improvement in the technology for improving the catalytic activity of the catalyst for dehydrogenation reaction in promoting the catalytic activity of the dehydrogenation reaction at low temperature.
[0012] Solutions for solving problems
[0013] The present disclosure can be implemented in the following ways.
[0014] (1) According to one embodiment of the present disclosure, a catalyst for dehydrogenation reaction is provided. The catalyst for dehydrogenation reaction comprises: a main phase, which is a general formula (A 1-x A' x )(Zr 1-y-z B y B' z ) 3-δ(wherein A is at least one element selected from alkaline earth metals, A' is at least one element selected from lanthanum (La) and yttrium (Y), B is at least one element selected from titanium (Ti) and cerium (Ce), B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In) and neodymium (Nd), and 0≤x≤0.4, 0.3≤(1-z)≤1, 0≤y, 0<(1-yz), δ represents the amount of oxygen deficiency) is composed of a perovskite-type oxide represented by the general formula AB'2O4, A2B'2O5, A3B'4O9 (wherein A and B' are elements common to A and B' constituting the above-mentioned perovskite-type oxide). According to the catalyst for dehydrogenation reaction in this embodiment, the heat resistance of the catalyst for dehydrogenation reaction can be improved.
[0015] (2) In the above-mentioned catalyst for dehydrogenation reaction, the above-mentioned A may be barium (Ba), the above-mentioned B' may be scandium (Sc), and the above-mentioned subphase may be composed of barium scandate (at least one of the three composite oxides of BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9). If such a structure is formed, the catalytic activity as a catalyst for dehydrogenation reaction can be further improved.
[0016] (3) In the above-described dehydrogenation reaction catalyst, the subphase may be composed of Ba3Sc4O9. With such a structure, a catalyst having high catalytic activity as a dehydrogenation reaction catalyst can be easily obtained.
[0017] (4) In the above-mentioned catalyst for dehydrogenation reaction, the main phase may be BaZr 1-z Sc z O 3-δ (wherein 0.1≤z≤0.7) If such a structure is adopted, the catalytic activity as a dehydrogenation reaction catalyst can be further improved.
[0018] (5) In the above-mentioned catalyst for dehydrogenation reaction, in the powder X-ray diffraction spectrum using CuKα rays, the perovskite-type oxide constituting the main phase has a first peak with the highest peak intensity in the range of diffraction angle 2θ = 29.5-30.5°, and the composite oxide constituting the subphase has a second peak with the highest peak intensity in the range of diffraction angle 2θ = 30.6-31.0°, and the ratio of the intensity of the second peak to the intensity of the first peak can be 0.04 or more. With such a configuration, the catalytic activity as a catalyst for dehydrogenation reaction can be further improved.
[0019] (6) In the above-mentioned dehydrogenation reaction catalyst, the subphase may be composed of any one of the above-mentioned three composite oxides. With such a structure, a catalyst having high catalytic activity as a dehydrogenation reaction catalyst can be easily obtained.
[0020] (7) The dehydrogenation reaction catalyst of the above embodiment may be a methane oxidative coupling catalyst for producing hydrocarbons having a carbon number of 2 or more from methane. With such a configuration, the heat resistance of the methane oxidative coupling catalyst can be improved.
[0021] (8) In another embodiment of the catalyst for dehydrogenation reaction, the spectrum of O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy is divided into a first curve and a second curve by peak separation fitting processing, the first curve having a first peak corresponding to a local maximum value in the range of 525-530 eV for bonding energy, and the second curve having a second peak corresponding to a local maximum value in the range of 530-535 eV for bonding energy, and when the area of the convex portion including the first peak in the first curve is set as the first peak area, and the area of the convex portion including the second peak in the second curve is set as the second peak area, the ratio of the second peak area to the first peak area is greater than 1. According to the catalyst for dehydrogenation reaction of this embodiment, the oxygen-adsorbing substance becomes easy to be adsorbed on the surface of the catalyst for dehydrogenation reaction, and thus the catalytic activity as the catalyst for dehydrogenation reaction can be improved.
[0022] (9) The dehydrogenation reaction catalyst of the above embodiment has oxygen defects. With such a structure, the amount of oxygen-adsorbed species on the surface of the dehydrogenation reaction catalyst can be increased, and thus the catalytic activity as the dehydrogenation reaction catalyst can be further improved.
[0023] (10) In the above-mentioned dehydrogenation reaction catalyst, the main phase of the catalyst is a perovskite structure. With such a structure, the catalytic activity as a dehydrogenation reaction catalyst can be further improved.
[0024] (11) In the above-mentioned embodiment of the catalyst for dehydrogenation reaction, the specific surface area measured by the BET method is 10 m 2 With such a configuration, the amount of oxygen-adsorbed species on the surface of the dehydrogenation reaction catalyst can be increased, and thus the catalytic activity as the dehydrogenation reaction catalyst can be further improved.
[0025] (12) The dehydrogenation reaction catalyst of the above embodiment is a methane oxidative coupling catalyst for producing hydrocarbons having a carbon number of 2 or more from methane. With such a configuration, the catalytic activity of the methane oxidative coupling catalyst can be improved.
[0026] (13) Furthermore, another embodiment of the catalyst for dehydrogenation reaction is a catalyst of the general formula (La 1-x M1 x )M2O 3-δ (wherein, M1 is at least one element selected from alkaline earth metals, M2 is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and gallium (Ga), and δ represents the amount of oxygen deficiency, satisfying 0≤x≤0.6). The catalyst for dehydrogenation reaction according to this embodiment can improve the catalytic activity of the catalyst for dehydrogenation reaction that promotes the dehydrogenation reaction at low temperature.
[0027] (14) In the above-mentioned dehydrogenation reaction catalyst, the above-mentioned M1 is strontium (Sr) or barium (Ba). If such a structure is formed, the catalytic activity as a dehydrogenation reaction catalyst can be further improved, and the catalytic activity of promoting the dehydrogenation reaction at a relatively low temperature can be further improved.
[0028] (15) The dehydrogenation reaction catalyst of the above embodiment is a methane oxidative coupling catalyst for producing hydrocarbons having a carbon number of 2 or more from methane. With such a configuration, the catalytic activity of the methane oxidative coupling catalyst at low temperatures can be improved.
[0029] The present disclosure can be implemented in various forms other than those described above, for example, in the form of a method for producing a dehydrogenation reaction catalyst, an apparatus including a dehydrogenation reaction catalyst, an ethylene production apparatus including a methane oxidative coupling catalyst, and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is an explanatory diagram showing a phase diagram of an oxide containing barium and scandium.
[0031] Figure 2 This is a first explanatory diagram showing an example of a reaction performed on a dehydrogenation reaction catalyst.
[0032] Figure 3 This is a second explanatory diagram showing an example of a reaction performed on a dehydrogenation reaction catalyst.
[0033] Figure 4 The figure shows the chemical formulas of various dehydrogenation reactions that can be promoted by the dehydrogenation reaction catalyst.
[0034] Figure 5 This is the first diagram showing the characteristics of the dehydrogenation reaction catalyst according to the first embodiment.
[0035] Figure 6 FIG. 2 is a second diagram showing the characteristics of the dehydrogenation reaction catalyst according to the first embodiment.
[0036] Figure 7This is a diagram showing an XRD pattern of the dehydrogenation reaction catalyst according to the first embodiment.
[0037] Figure 8 This is an explanatory diagram showing an XRD pattern of the dehydrogenation reaction catalyst according to the first embodiment.
[0038] Fig. 9 1 is a first diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0039] Fig.10 This is a diagram showing the temperature change of the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0040] Fig.11 The second figure shows the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0041] Fig.12 FIG. 1 is a SEM image showing a dehydrogenation reaction catalyst according to the first embodiment.
[0042] Fig.13 FIG. 2 is a SEM image showing the dehydrogenation reaction catalyst according to the first embodiment.
[0043] Fig.14 This is a diagram showing the specific surface area of the dehydrogenation reaction catalyst according to the first embodiment.
[0044] Fig.15 FIG. 1 is a first diagram showing an XPS spectrum of the dehydrogenation reaction catalyst according to the first embodiment.
[0045] Fig.16 FIG2 is a second diagram showing the XPS spectrum of the dehydrogenation reaction catalyst according to the first embodiment.
[0046] Fig.17 The third figure shows the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0047] Fig.18 This is a diagram for explaining a method for calculating the XPS ratio.
[0048] Fig.19 FIG. 4 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0049] Fig. 20 FIG5 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the first embodiment.
[0050] Fig.21 FIG6 is a sixth diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the second embodiment. DETAILED DESCRIPTION
[0051] <First embodiment>
[0052] [Dehydrogenation reaction catalyst]
[0053] The catalyst for dehydrogenation reaction in this embodiment is a composite oxide comprising: a main phase having a perovskite-type oxide crystal structure represented by the general formula (1) shown below; and a subphase having at least one of three composite oxides represented by the general formulas (2a) to (2c) shown below.
[0054] (A 1-x A' x )(Zr 1-y-z B y B' z ) 3-δ …(1)
[0055] AB'2O4…(2a)
[0056] A2B'2O5…(2b)
[0057] A3B'4O9…(2c)
[0058] In the above formula (1), A is at least one element selected from alkaline earth metals, A' is at least one element selected from lanthanum (La) and yttrium (Y), B is at least one element selected from titanium (Ti) and cerium (Ce), and B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In) and neodymium (Nd). In formula (1), x, y and z satisfy the relationship of formulas (3a) to (3d) shown below. δ represents the amount of oxygen deficiency for obtaining electrical neutrality, for example, 0≤δ≤0.5.
[0059] 0≤x≤0.4…(3a)
[0060] 0.3≤(1-z)≤1…(3b)
[0061] 0≤y…(3c)
[0062] 0<(1-yz)…(3d)
[0063] In the above formulae (2a) to (2c), A and B' are elements common to A and B' constituting the perovskite type oxide represented by formula (1).
[0064] In addition, in the catalyst for dehydrogenation reaction of the present embodiment, the spectrum of the O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy is divided into a first curve and a second curve by peak separation fitting processing, the first curve having a first peak corresponding to a local maximum value in the range of 525-530 eV for bonding energy, the second curve having a second peak corresponding to a local maximum value in the range of 530-535 eV for bonding energy, and when the area of the convex portion including the first peak in the first curve is the first peak area and the area of the convex portion including the second peak in the second curve is the second peak area, the ratio of the second peak area to the first peak area is greater than 1. In the spectrum of the O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy, the first peak area is derived from lattice oxygen species at the surface of the catalyst for dehydrogenation reaction, and the second peak area is derived from adsorbed oxygen species at the surface of the catalyst for dehydrogenation reaction. That is, the ratio of the second peak area to the first peak area being greater than 1 means that a large amount of activated oxygen-adsorbing substances exist in the dehydrogenation reaction catalyst. Thus, the dehydrogenation reaction is promoted. The details of the "first peak area" and the "second peak area" are described later.
[0065] The dehydrogenation reaction catalyst having a ratio of the second peak area to the first peak area greater than 1 preferably has an oxygen defect. Specifically, for example, a composition formula of Ba(Zr 1-x Y x ) 3-δ The larger the value of x of the dehydrogenation reaction catalyst shown, the easier it is to have oxygen defects due to charge compensation. As a result, the amount of activated oxygen adsorbed substances can be increased on the surface of the dehydrogenation reaction catalyst. In addition, the dehydrogenation reaction catalyst having a ratio of the second peak area to the first peak area greater than 1 is expected to have a specific surface area of 10m2 measured by the BET method. 2 Thereby, the amount of the activated oxygen-adsorbing species on the surface of the dehydrogenation reaction catalyst can be increased.
[0066] In the catalyst for dehydrogenation reaction of the present embodiment, at least the perovskite-type oxide of formula (1) constituting the main phase has activity as a catalyst for dehydrogenation reaction. Here, "main phase" refers to a phase having a peak intensity ratio of 50% or more in a powder X-ray diffraction spectrum using CuKα rays. In addition, the catalyst for dehydrogenation reaction of the present embodiment has a subphase composed of at least one of the three composite oxides represented by formulas (2a) to (2c) in addition to the above-mentioned main phase, and as a result, the heat resistance of the catalyst is improved.
[0067] [Perovskite-type oxide constituting the main phase]
[0068] As described above, in the dehydrogenation reaction catalyst of the present embodiment, at least the perovskite type oxide of formula (1) constituting the main phase has activity as a dehydrogenation reaction catalyst. The perovskite type oxide of formula (1) will be further described below.
[0069] The perovskite-type oxide of formula (1) contains at least one element selected from alkaline earth metals at the so-called A site of the perovskite structure. The alkaline earth metal is preferably an element selected from barium (Ba), calcium (Ca), and strontium (Sr). Hereinafter, the alkaline earth metal element contained in the above-mentioned A site is also referred to as "element A". The perovskite-type oxide of formula (1) may also contain at least one element of lanthanum (La) and yttrium (Y) at the A site of the perovskite structure. Among them, lanthanum (La) and yttrium (Y) are not required. Hereinafter, lanthanum (La) and yttrium (Y) contained in the above-mentioned A site are also referred to as "element A'". In the catalyst for dehydrogenation reaction of this embodiment, the contents of element A and element A' in formula (1) satisfy formula (3a).
[0070] In addition, the perovskite oxide of formula (1) contains zirconium (Zr) at the so-called B site of the perovskite structure. The perovskite oxide may further contain at least one element of titanium (Ti) and cerium (Ce) at the B site. Among them, titanium (Ti) and cerium (Ce) are not required. Hereinafter, the titanium (Ti) and cerium (Ce) contained in the above-mentioned B site are also referred to as "element B". The perovskite oxide of formula (1) may further contain at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In) and neodymium (Nd) at the B site of the perovskite structure. Among them, at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In) and neodymium (Nd) is not required. Hereinafter, at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In) and neodymium (Nd) contained in the above-mentioned B site is also referred to as "element B'". In the perovskite-type oxide of formula (1), the contents of Zr, element B and element B' in formula (1) satisfy formulas (3b) to (3d).
[0071] In the perovskite-type oxide of formula (1), it is desirable that x satisfies the following formula (3e). This can further improve the catalytic activity as a dehydrogenation reaction catalyst that promotes the dehydrogenation reaction.
[0072] 0≤x≤0.2…(3e)
[0073] The perovskite oxide of formula (1) preferably has a perovskite structure represented by the following general formula (4): This can further improve the catalytic activity as a dehydrogenation reaction catalyst that promotes the dehydrogenation reaction.
[0074] BZ1-z B' z O 3-δ …(4)
[0075] Here, B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), indium (In) and neodymium (Nd). In this case, it is particularly desirable that B' is scandium (Sc), that is, the perovskite oxide of formula (4) is BaZr 1-z Sc z O 3-δ (wherein 0.1≤z≤0.7) This further improves the catalytic activity of the catalyst for the dehydrogenation reaction, which promotes the dehydrogenation reaction.
[0076] Furthermore, the perovskite-type oxide of formula (1) has catalytic activity as a dehydrogenation reaction catalyst that promotes the dehydrogenation reaction, and has both proton conductivity and at least one of electron conductivity and hole conductivity.
[0077] [Compound oxide constituting the subphase]
[0078] As described above, the dehydrogenation reaction catalyst of the present embodiment has a subphase composed of at least one of the three composite oxides represented by formulas (2a) to (2c), and due to such a structure, the heat resistance is improved. Specifically, for example, when the dehydrogenation reaction catalyst is used under temperature conditions of 800° C. or higher, the decrease in the catalytic activity of the dehydrogenation reaction catalyst that promotes the dehydrogenation reaction can also be suppressed. It should be noted that the subphase is more preferably composed of any one of the three composite oxides represented by formulas (2a) to (2c).
[0079] In the formulas (2a) to (2c), A and B' are elements common to A and B' of the perovskite-type oxide of the formula (1) constituting the main phase. As described later, such a composite oxide of the secondary phase can be formed together with the perovskite-type oxide of the main phase by mixing raw material powders of the perovskite-type oxide of the formula (1) constituting the main phase and calcining them at a relatively high temperature of about 1300-1600°C when manufacturing a catalyst for a dehydrogenation reaction. Whether the secondary phase is composed of any of the composite oxides represented by the formulas (2a) to (2c) is determined by the types of elements contained in the A site and the B site of the perovskite-type oxide of the formula (1). In addition, whether the secondary phase is composed of any of the composite oxides represented by the above-mentioned composite oxides can also be changed according to the mixing ratio when the raw material powders of the main phase are mixed to manufacture the catalyst for a dehydrogenation reaction.
[0080] In the catalyst for dehydrogenation reaction of this embodiment, it is preferred that element A in formula (1) is barium (Ba), element B' is scandium (Sc), and the subphase is composed of at least one of three composite oxides belonging to barium scandate, BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9. In this case, it is particularly preferred that the subphase is composed of Ba3Sc4O9.
[0081] Figure 1 This is an explanatory diagram showing a phase diagram of an oxide containing barium (Ba) and scandium (Sc) as an example (source: Kovba L.M., Lykova LN, Paromiva MV, Kalinina TA (1981). X-Ray and thermographic investigation of compounds in the BaO-Sc2O3 system. Dokl. Akad. Nauk SSSR, 260, 924-927). Figure 1 As shown, as a composite oxide containing barium (Ba) and scandium (Sc), it is understood that three composite oxides of BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9 can be formed. From the composite oxides that appear in the phase diagram, it can be said that when an alkaline earth metal other than barium (Ba) is used as element A and the above element other than scandium (Sc) is used as element B', the three composite oxides shown in formulas (2a) to (2c) can also be formed.
[0082] In the powder X-ray diffraction spectrum using CuKα rays, when the maximum peak of the perovskite oxide constituting the main phase in the dehydrogenation reaction catalyst of this embodiment is set as the first peak and the maximum peak of the composite oxide constituting the subphase is set as the second peak, the ratio of the intensity of the second peak to the intensity of the first peak is preferably 0.02 or more, more preferably 0.03 or more, and further preferably 0.04 or more. In this way, by ensuring the ratio of the composite oxide constituting the subphase, it is easy to improve the heat resistance of the dehydrogenation reaction catalyst. For example, the perovskite oxide constituting the main phase is BaZr 1-z Sc z O 3-δ When the composite oxide constituting the subphase is Ba3Sc4O9, in the powder X-ray diffraction spectrum using CuKα rays, the first peak is obtained in the range of diffraction angle 2θ=29.5-30.5°, and the second peak is obtained in the range of diffraction angle 2θ=30.6-31.0°.
[0083] According to the dehydrogenation reaction catalyst of the present embodiment constructed as above, by having a main phase having a perovskite-type oxide crystal structure represented by the above formula (1) and a subphase having at least one of the three composite oxides represented by the above formulas (2a) to (2c), the catalytic activity as a dehydrogenation reaction catalyst that promotes the dehydrogenation reaction of hydrogen from the compound can be improved, and the heat resistance of the dehydrogenation reaction catalyst can be improved. In the dehydrogenation reaction catalyst of the present embodiment, the catalytic activity that promotes the dehydrogenation reaction is mainly achieved by the perovskite-type oxide constituting the main phase. In such a dehydrogenation reaction catalyst, by also having a subphase having at least one of the three composite oxides represented by the formulas (2a) to (2c), even when the dehydrogenation reaction catalyst is used under higher temperature conditions, the decrease in the catalytic activity that promotes the dehydrogenation reaction can be suppressed.
[0084] The catalyst for dehydrogenation reaction of this embodiment can promote various dehydrogenation reactions in which hydrogen is separated from a compound. As a dehydrogenation reaction, for example, the oxidative coupling of methane (OCM) reaction for producing hydrocarbons having a carbon number of 2 or more from methane can be cited. In addition, various reactions in which hydrogen is generated by dehydrogenation reactions of various hydrocarbon compounds including hydrocarbons and alcohols can be cited. Specifically, a steam reforming reaction in which hydrogen is generated from the above-mentioned hydrocarbon compounds and water vapor, a partial oxidation reaction in which hydrogen is generated from the above-mentioned hydrocarbon compounds, a conversion reaction in which carbon monoxide and water vapor generated together with hydrogen in the above-mentioned partial oxidation reaction are used to generate carbon dioxide and hydrogen, and the like can be cited.
[0085] Figure 2 This is a first explanatory diagram showing an example of a reaction performed on a dehydrogenation reaction catalyst. Figure 3 This is a second explanatory diagram showing an example of a reaction performed on a dehydrogenation reaction catalyst. Figure 2 and Figure 3 This is an explanatory diagram showing an example of a methane oxidative coupling reaction performed on a methane oxidative coupling catalyst in the case where the catalyst for dehydrogenation reaction of the present embodiment is a methane oxidative coupling catalyst as an example of a reaction including a dehydrogenation reaction. When a dehydrogenation reaction in which hydrogen is separated from a compound is performed, generally, the covalent bond between the carbon atoms and the hydrogen atoms constituting the compound is cut. It is believed that the catalyst for dehydrogenation reaction of the present embodiment exhibits high activity in promoting dehydrogenation reactions by promoting such reactions. It is believed that in the methane oxidative coupling reaction, the reaction of producing methyl radicals from methane shown in the following formula (5) proceeds, and further, the reactions of the following formulas (6) and (7) (refer to Figure 2 ), the following reactions of formula (8) and formula (9) (refer to Figure 3) is carried out, thereby producing C2 hydrocarbons such as ethylene. The overall reaction of producing ethylene by methane oxidative coupling reaction is represented by the following formula (10).
[0086] CH4 → ·CH3+H + +e - … (5)
[0087] 2·CH3+1 / 2O2 → C2H4+H2O … (6)
[0088] 1 / 2O2+2H + +2e - → H2O … (7)
[0089] 2. CH3 → C2H6 → C2H4+2H + +2e - … (8)
[0090] O2+4H + +4e - →2H2O…(9)
[0091] 2CH4+O2 → C2H4+2H2O … (10)
[0092] Here, the bonding energy of the covalent bond between the carbon atom and the hydrogen atom in methane is 104kcal / mol, which is an extremely stable bond. Therefore, in the methane oxidative coupling reaction, it is generally believed that the reaction of generating methyl radicals by dehydrogenation from methane with stable covalent bonds (the reaction of the above formula (5)) is the rate-controlling process. In at least the main phase of the catalyst for dehydrogenation reaction of the present embodiment, the activity of promoting the reaction of cutting the covalent bond in hydrogen such as the reaction of generating methyl radicals from methane is high, so it is believed that the dehydrogenation reaction such as the methane oxidative coupling reaction accompanied by the cutting of the covalent bond in hydrogen can be widely promoted. Furthermore, at least the main phase of the catalyst for dehydrogenation reaction of the present embodiment is a proton conductor as described above, which can make the hydrogen of the molecule containing hydrogen protonated and moved. Therefore, it is believed that the activity of promoting the reaction accompanied by the cutting of the covalent bond containing hydrogen is high, and the dehydrogenation reaction such as the methane oxidative coupling reaction accompanied by the cutting of the covalent bond containing hydrogen can be widely promoted.
[0093] Figure 2 and Figure 3 In the above, the site where the reaction of formula (5) from methane to methyl radical proceeds is represented as an "oxidation site". Figure 2 and Figure 3 In the figure, the state in which the reaction of formula (6) or formula (8) in which ethylene is further generated from a methyl radical at the oxidation site is shown. Figure 2 and Figure 3In the reaction of formula (7) or formula (9) in which the protons and electrons generated together with the methyl radical in formula (5) are used to generate water, the site is represented as a "reduction site". In this way, when the reaction of the dehydrogenation reaction in the catalyst for dehydrogenation reaction of the present embodiment is carried out, it is usually accompanied by the acceptance of protons and electrons. Therefore, in order to improve the catalytic activity, the catalyst for dehydrogenation reaction is expected to have high proton conductivity and electron conductivity (including hole conductivity) in addition to promoting the high activity of the reaction of formula (5) belonging to the rate-controlling process. Specifically, it is expected that the proton conductivity, the proton migration number, or the electron conductivity (including the hole migration number) and the electron migration number (including the hole migration number) are higher. Moreover, as a whole catalyst for dehydrogenation reaction, it is expected that the total of the proton conductivity and the electron conductivity (including the hole conductivity), that is, the total conductivity, is also higher.
[0094] From such a viewpoint, for example, it is desirable that the total conductivity of the main phase of the dehydrogenation reaction catalyst of the present embodiment is 1.0×10 -5 S / cm or more. In addition, the proton conductivity of the main phase is preferably 1.0×10 -4 S / cm or more. In addition, it is desired that the proton migration number of the main phase is greater than 0.01. In addition, it is desired that the total of the electron migration number and the hole migration number of the main phase is greater than 0.01. In addition, in the main phase, it is desired that the proton migration number, and the total of the electron migration number and the hole migration number are respectively greater than 0.10. In contrast, if the electron conductivity (including the hole conductivity) is excessively increased, for example, in the methane oxidative coupling reaction, the overoxidation of methane, that is, the complete oxidation reaction of methane to produce carbon dioxide and water becomes easy to proceed, and there is a possibility that the reaction of methane to produce ethylene is suppressed. Therefore, it is desired that the total conductivity of the main phase of the catalyst for the dehydrogenation reaction is 1.0×10 -1 S / cm or less, and the sum of the electron transfer number and the hole transfer number of the main phase is preferably 0.95 or less. The perovskite type oxide constituting the main phase of the dehydrogenation reaction catalyst easily satisfies the above numerical range by satisfying the above formula (1) and formulas (3a) to (3d).
[0095] [Other dehydrogenation reactions]
[0096] Figure 4 This is an explanatory diagram showing examples of various dehydrogenation reactions that can be promoted by the dehydrogenation reaction catalyst of the present embodiment. The dehydrogenation reaction catalyst of the present embodiment can promote various reactions depending on the raw materials (reactants) used. Figure 4In formulas (11) to (22), a reaction is shown in which reactants containing at least one of methane and methane derivatives (hereinafter also referred to as "methanes") are bonded. Such a reaction is also referred to as a "methane oxidative coupling reaction". Furthermore, the dehydrogenation reaction catalyst of this embodiment that promotes the oxidative coupling reaction of alkanes is also referred to as a "methane oxidative coupling catalyst". It should be noted that Figure 4 In the formulae (13) to (22), A and B contained in the methane derivative represent atoms or atomic groups that are substituents replacing hydrogen in the methane hydrocarbon molecule, and n is an integer of 2 or more. Figure 4 The methane derivatives shown are obtained by replacing one or two hydrogen atoms contained in the methane hydrocarbon molecule with the above-mentioned substituents. When one molecule has a substituent A and a substituent B, A and B may be the same substituent or different substituents. Examples of the substituents represented by A or B include halogen elements, hydroxyl groups (-OH), and phenyl groups (-C6H5).
[0097] Figure 4 In the above formula, (11) represents the reaction of producing ethylene from methane, similarly to (10). (12) represents the reaction of producing polyethylene by further polymerization. Unlike (10), formulas (11) to (22) only show the changes of methane and methane derivatives in the molecules involved in the reaction.
[0098] Formulas (11) and (12) represent reactions using methane as a reactant. Formulas (13) and (14) represent reactions using a methane derivative represented by BACH2 as a reactant. Formulas (15) and (16) represent reactions using a methane derivative represented by ACH3 as a reactant. Formulas (17) and (18) represent reactions using a methane derivative represented by ACH3 and methane as reactants. Formulas (19) and (20) represent reactions using a methane derivative represented by ACH3 and a methane derivative represented by CA2H2 as reactants. Formulas (21) and (22) represent reactions using a methane derivative represented by CABH2 and methane as reactants.
[0099] In addition, formula (11), formula (13), formula (15), formula (17), formula (19) and formula (21) represent reactions for producing hydrocarbons (ethylene) or ethylene derivatives (hereinafter, also referred to as "C2 hydrocarbons") having a carbon number of 2 using reactants selected from hydrocarbons having a carbon number of 1 (methane) and methane derivatives (hereinafter, also referred to as "C1 hydrocarbons"). Formula (12), formula (14), formula (16), formula (18), formula (20) and formula (22) represent reactions for producing polymers using reactants selected from C1 hydrocarbons. When producing polymers, after C2 hydrocarbons are produced from C1 hydrocarbons, these C2 hydrocarbons may be further polymerized with each other, or C1 hydrocarbons may be polymerized sequentially at the ends of the molecules to form a polymer, or both reactions may be performed.
[0100] right Figure 4 When the reaction shown is further specifically described, for example, in formula (14), if both A and B of the substituents are fluorine atoms (F), polytetrafluoroethylene (PTFE) is obtained as a product. In formula (18), if substituent A is a chlorine atom (Cl), polyvinyl chloride (PVC) is obtained as a product, if substituent A is a hydroxyl group (-OH), polyvinyl alcohol (PVOH) is obtained as a product, and if substituent A is a phenyl group (-C6H5), polystyrene (PS) is obtained as a product. In formula (22), if both A and B of the substituents are fluorine atoms (F), polyvinylidene fluoride (PVDF) is obtained as a product, and if both A and B of the substituents are chlorine atoms (Cl), polyvinylidene chloride (PVDC) is obtained as a product. In addition, in formula (22), if substituent A is a methyl group (-CH3) and substituent B is a methoxycarbonyl group (-COOCH3), polymethyl methacrylate (PMMA) is obtained as a product.
[0101] Figure 4 In the embodiment, a methane oxidative coupling reaction is shown, but the dehydrogenation reaction catalyst of the present embodiment can also be used to promote dehydrogenation reactions other than methane oxidative coupling reactions. As a dehydrogenation reaction promoted by the dehydrogenation reaction catalyst of the present embodiment, for example, a reaction in which reactants containing at least one of alkanes and alkane derivatives (hereinafter also referred to as "alkanes") are bonded can be cited. Such a reaction is also referred to as an "alkane oxidative coupling reaction" together with the methane oxidative coupling reaction described above. The dehydrogenation reaction catalyst of the present embodiment that promotes the alkane oxidative coupling reaction is also referred to as an "alkane oxidative coupling catalyst". The carbon number of the alkanes of the reactants of the alkane oxidative coupling reaction promoted by the dehydrogenation reaction catalyst of the present embodiment can be set to 1 to 10, preferably 1 to 5, and more preferably 1 or 2. It should be noted that the alkane derivative provided for the alkane oxidative coupling reaction is formed by replacing the hydrogen contained in the alkane molecule with the substituent, but has a covalent bond between the carbon atom and the hydrogen atom that is the object of dehydrogenation.
[0102] The dehydrogenation reaction catalyst of this embodiment can also be used to promote hydrogen reactions other than alkane oxidative coupling reactions. Other dehydrogenation reactions promoted by the dehydrogenation reaction catalyst of this embodiment include, for example: Figure 4The dehydrogenation reaction of alkanes exemplified in formula (23), and the dehydrogenation reaction of alcohols or alcohol derivatives (hereinafter also referred to as "alcohols") exemplified in formulas (24) and (25). In formulas (23) to (25), A and B represent hydrogen, or, as in formulas (13) to (22), represent atoms or atomic groups that are substituents that replace hydrogen. Formula (23) represents a reaction of generating olefins or olefin derivatives from alkanes. Formula (24) represents a reaction of generating aldehydes from alcohols, and formula (25) represents a reaction of generating ketones from alcohols. In this way, the dehydrogenation reaction catalyst of this embodiment can be used as a catalyst that promotes various dehydrogenation reactions.
[0103] [Method for producing a dehydrogenation reaction catalyst]
[0104] The catalyst for dehydrogenation reaction of the present embodiment can be prepared, for example, by a solid phase reaction method. Specifically, a powder of a metal oxide, a metal carbonate, or the like, which is a raw material of the main phase represented by formula (1), is mixed in a ball mill or the like using a solvent such as ethanol, and then the solvent is removed by drying and calcined. At this time, calcination is performed at a relatively high temperature of about 1300-1600° C., so that a composite oxide having both the main phase represented by formula (1) and a secondary phase of at least one of the three composite oxides represented by formulas (2a) to (2c) can be obtained.
[0105] As a method for making composite oxides, in addition to the solid phase reaction method, various methods such as complex polymerization, coprecipitation, sol-gel method are also known. In particular, the complex polymerization method can mix raw materials at the molecular level, and therefore, it is known that the manufacturing method as a catalyst is excellent. However, the structure in the complex polymerization method is easily changed due to heat, and in the case of calcining at a high temperature such as described above, it is easy to produce changes such as the particle size becoming larger, and as a result, the performance as a catalyst may be reduced. In contrast, the solid phase reaction method is not easily affected by the structural changes caused by heat, and even if it is calcined at a high temperature such as described above, the performance as a catalyst can be suppressed. Moreover, in the case of manufacturing a dehydrogenation reaction catalyst by a solid phase reaction method accompanied by calcination at the above high temperature, the structure of the composite oxide is stabilized under the high temperature calcination condition, and therefore, when the obtained dehydrogenation reaction catalyst is used at a temperature lower than the calcination temperature (to carry out the dehydrogenation reaction), the deterioration of the structural changes including the volatilization of the constituent elements is suppressed. Therefore, for example, even when the catalyst temperature rises rapidly as an exothermic reaction including a dehydrogenation reaction proceeds, the occurrence of inconveniences such as deactivation of the dehydrogenation reaction catalyst can be suppressed, and the heat resistance and durability of the dehydrogenation reaction catalyst can be improved.
[0106] <Example 1>
[0107] Figure 5FIG. 1 is a first diagram showing the characteristics of the dehydrogenation reaction catalyst according to the present embodiment. Figure 6 FIG. 2 is a diagram showing the characteristics of the dehydrogenation reaction catalyst according to the present embodiment. Figure 5 and Figure 6 This is an explanatory diagram showing the results of preparing 34 composite oxides of samples A1 to A34 and investigating their performance. Here, the performance as a catalyst for dehydrogenation reaction is evaluated as a methane oxidative coupling catalyst. Among samples A1 to A34, samples A1 to A29 correspond to the main phase in the catalyst for dehydrogenation reaction of the embodiment described, and are perovskite-type oxides that satisfy the above-described formula (1) and formulas (3a) to (3d). Samples A30 to A34 are composite oxides that do not satisfy at least any one of formulas (1) and (3a) to (3d). These composite oxides of samples A1 to A34 are prepared by a complex polymerization method. It should be noted that in the following description and the descriptions in the figures, the number of oxygen atoms in the formula is sometimes simplified as "O3", but these descriptions are different from "O 3-δ " has the same meaning, and δ is not strictly represented as 0. The following describes the composition, manufacturing method, evaluation method and performance evaluation results of each sample.
[0108] [Preparation of Sample A1]
[0109] The catalyst of sample A1 (BaZr 0.8 Sc 0.2 O3) was prepared by complex polymerization method. Barium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), zirconium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), and scandium nitrate (manufactured by Alfa Aesar) were used as raw material powders. The ratio of the metal elements was BaZr 0.8 Sc 0.2 These raw material powders are weighed in the manner of a composition ratio in O3. Then, for the above raw material powders, citric acid aqueous solution and propylene glycol are added in a manner of a ratio of metal element: citric acid: propylene glycol = 1:3:3 (mol ratio), and the mixture is stirred and mixed at 80°C for 1 hour. Then, the solution is slowly heated to 300°C to obtain a polymer in which each metal element is dispersed. Furthermore, the obtained polymer is heat-treated at 400°C for 2 hours to carbonize it, and the obtained product is crushed in an agate mortar to obtain a catalyst powder precursor. The obtained catalyst powder precursor is heat-treated at a temperature ( Figure 5 and Figure 6The sample was heat treated at 1200° C. for 6 hours (“T_treat” shown in the figure) to obtain a powdery catalyst for dehydrogenation reaction, namely Sample A1.
[0110] For sample A1 and samples A2 to A34 described later, the powdered methane oxidative coupling catalyst obtained had the desired composition, which was confirmed by analysis based on the powder XRD method. Specifically, the results of the analysis based on the powder XRD method were confirmed by obtaining a perovskite structure and by not confirming the peaks of the raw material powder or the elemental oxide (oxide containing only one element other than oxygen), carbonate, etc. derived from the raw material powder. In addition, for sample A1 and samples A2 to A34 described later, the specific surface area of the powdered methane oxidative coupling catalyst obtained was measured by the gas adsorption method, and the results confirmed that they were all 5m 2 / g~10m 2 / g range.
[0111] [Preparation of Samples A2 to A34]
[0112] To become Figure 5 and Figure 6 The types and weighing amounts of the catalyst raw material powders and the heat treatment temperature of the catalyst powder precursor were adjusted to the composition ratios of the composition formulas of samples A2 to A34 shown in FIG. Figure 5 and Figure 6 The temperature shown ( Figure 5 and Figure 6Powdered dehydrogenation reaction catalysts as Samples A2 to A34 were obtained in the same manner as Sample A1 except for the above. In order to add barium, zirconium, scandium, yttrium, ytterbium, indium, neodymium, cerium, lanthanum, strontium, calcium, iron, and titanium as constituent elements, barium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), zirconium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), scandium nitrate (manufactured by Alfa Aesar), yttrium nitrate (manufactured by Sigma-Aldrich), ytterbium nitrate (manufactured by Sigma-Aldrich), indium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), neodymium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), cerium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), lanthanum nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), strontium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), calcium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), iron nitrate (manufactured by Sigma-Aldrich), and titanium tetraisopropoxide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) were used as raw material powders.
[0113] [Determination of total conductivity]
[0114] Samples A1 to A34 were press-formed into rectangular parallelepipeds, sintered at 1600°C for 6 hours, and platinum wires were wound at 4 locations. Platinum paste (TR-7905 manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) was applied thereon, and baked at 1000°C for 1 hour to form test samples. Each test sample was placed in a tubular electric furnace, and heated while hydrogen humidified by a bubbler was circulated. The total conductivity ( Figure 5 and Figure 6 Here, the relative density of each sintered body used for the measurement of the total conductivity was measured by the Archimedean method, and it was confirmed that all the sintered bodies had a relative density of 96% or more.
[0115] [Measurement of proton transfer number and electron / hole transfer number, and calculation of proton conductivity]
[0116] Samples A1 to A34 were press-formed into disc shapes, sintered at 1600°C for 6 hours, and platinum paste was printed on both sides of the obtained discs with circular screens. The discs were baked at 1000°C for 1 hour to prepare test samples. The migration number measuring device includes two alumina tubes arranged vertically and aligned in the axial direction. The test sample is clamped between the two alumina tubes to ensure the gas tightness between the alumina tubes and the test sample. The portion containing the test sample is placed in an electric furnace to measure the migration number. Specifically, the space inside the two alumina tubes, one space separated by the test sample and the other space are heated to 750°C in the electric furnace while humidified hydrogen of different concentrations or humidification amounts flows therethrough. Then, the electromotive force generated between one surface and the other surface of the test sample is measured to determine the proton migration number ( Figure 5 and Figure 6 "TN_pro" shown), and electron / hole mobility ( Figure 5 and Figure 6 "TN_e / h" shown). Proton conductivity ( Figure 5 and Figure 6 The "C_pro" shown) was calculated by multiplying the total conductivity measured as above by the proton transfer number.
[0117] [Determination of C2 Yield]
[0118] 0.1 g of each sample A1 to sample A34 was weighed and placed in a fixed bed flow reactor. A mixed gas of methane, oxygen and nitrogen was heated to 750°C and set at a flow ratio of CH4:O2:N2=3.8:1:4 at 1 atmosphere and 45 cm 3 / min flow, and conduct catalytic activity test. This catalytic activity test is conducted in a state where each sample is heated to 750°C. The composition analysis of the gas input and the gas discharged from the device used in the catalytic activity test is conducted using a micro gas chromatograph (Agilent Technologies, Inc., 3000A). Using the results of the composition analysis, the C2 yield at 750°C is calculated ( Figure 5 and Figure 6 It should be noted that the C2 hydrocarbons in the gas discharged from the above device also include ethane and ethylene, but the proportion of ethylene in the obtained C2 hydrocarbons is about 60-70% in any sample (data not shown).
[0119] like Figure 5 and Figure 6As shown, Samples A1 to A29 show a higher C2 yield compared to Samples A30 to A34. It was confirmed that the perovskite-type oxide, which is the main phase of the catalyst for dehydrogenation reaction, has its catalytic activity as a catalyst for dehydrogenation reaction enhanced by satisfying the above-mentioned formulas (1) and (3a) to (3d). More specifically, for example, when the A-site of the perovskite structure contains an A' element (at least one of lanthanum (La) and yttrium (Y)), for example, based on the comparison between Sample A13 and Sample A32, it is considered that it is desirable to set "x ≤ 0.4" (formula (3a)) or "x ≤ 0.2" (formula (3e)). Moreover, based on the comparison between, for example, Sample A5 and Samples A13 and A14, and the comparison between Sample A21 and Sample A25, it was confirmed that especially by setting "x = 0", there is a tendency for the catalytic activity to increase. Furthermore, for example, based on the comparison between Sample A5 and Samples A18 and A21, the comparison between Sample A1 and Samples A20 and A23, and the comparison between Sample A6 and Samples A19 and A22, it was confirmed that by making the A element of the alkaline earth metal belonging to formula (1) be barium (Ba), there is a tendency for the catalytic activity to increase. That is, it was confirmed that it is desirable for the main phase of the catalyst for dehydrogenation reaction to have a perovskite structure represented by formula (4) of the above general formula.
[0120] In addition, for example, based on the comparison between Samples A1 to A5 and Sample A30, and the comparison between Samples A5 to A7 and Sample A31, it is considered that it is desirable to set "0 ≤ z ≤ 0.7". Moreover, for example, based on the comparison between Samples A1 to A4 and Sample A5, and the comparison between Samples A6 and A7 and Sample A5, it was confirmed that by setting "0 < z", especially by setting "0.2 ≤ z", there is a tendency for the catalytic activity to increase.
[0121] Figure 7 It is a diagram showing the XRD pattern of the catalyst for dehydrogenation reaction of the first embodiment. Figure 8 It is an explanatory diagram showing the XRD pattern of the catalyst for dehydrogenation reaction of the first embodiment. Figure 7 It is a diagram showing the XRD patterns of Sample A3 and Sample A35. Figure 8 For explaining Figure 7 the XRD pattern of Sample A35 shown. Samples A3 and A35 are represented by the same compositional formula (BaZr 0.4 Sc 0.6 O3), but the production methods are different. Here, the change in the performance of the catalyst for oxidative coupling of methane based on the presence or absence of the secondary phase in the catalyst for dehydrogenation reaction was evaluated.
[0122] [Production of Sample A35]
[0123] Sample A35 (BaZr 0.4 Sc0.6 O3) by solid phase reaction method. Barium carbonate (produced by Sakai Chemical Industry Co., Ltd.), zirconium oxide (produced by Daiichi Kizen Chemical Industry Co., Ltd.), and scandium oxide (produced by Alfa Aesar) are used as raw material powders. The ratio of the metal elements is BaZr 0.4 Sc 0.6 These raw material powders are weighed in the manner of the composition ratio in O3. Then, jade with a diameter of 5 mm and ethanol are added, and the mixture is mixed with a ball mill for 15 hours. After that, the ethanol component is dispersed, and after obtaining the solid component, it is sieved with a sieve with an opening of 250 μm. After that, it is calcined at 1300°C and 5 hours. Jade with a diameter of 5 mm and ethanol are added to the obtained powder and the ball mill is crushed again, and mixed for 15 hours. After that, the ethanol component is dispersed, and after obtaining the solid component, it is sieved with a sieve with an opening of 250 μm, and calcined at a heat treatment temperature of 1300°C and 5 hours. Jade with a diameter of 5 mm and ethanol are added to the obtained powder and the ball mill is crushed again, mixed for 15 hours, the ethanol component is dispersed, and after obtaining the solid component, it is sieved with a sieve with an opening of 250 μm, thereby obtaining a catalyst for dehydrogenation reaction as sample A35. It should be noted that sample A3 is prepared by complex polymerization as described above.
[0124] like Figure 7 As shown in FIG. 1 , in the XRD pattern of sample A35, peaks derived from the secondary phase that were not found in the XRD pattern of sample A3 were confirmed. That is, sample A35 has a secondary phase in addition to the main phase composed of the perovskite-type oxide of sample A3. Specifically, Figure 8 As shown in the XRD pattern of sample A35, the perovskite oxide (BaZr 0.4 Sc 0.6 O3) has the largest peak intensity in the range of diffraction angle 2θ = 29.5-30.5°, and the second peak intensity of the composite oxide (Ba3Sc4O9) constituting the secondary phase has the largest peak intensity in the range of diffraction angle 2θ = 30.6-31.0°. That is, it can be seen that in sample A35, the secondary phase of Ba3Sc4O9 is mixed in the main phase of the BaZrO3-based material. It should be noted that Figure 8 The ICDD (International Centre for Diffraction Data) database numbers used in the study are as follows: perovskite oxides are 00-001-0890, Ba3Sc4O9 is 00-031-0161. 1-x Sc x ) 3-δIn the figure, the peak of BaZrO3 shifts slightly to the low angle side. Figure 8 In the XRD pattern shown in the figure, the peak at the position of BaZrO3 is regarded as the peak of BaZr 0.4 Sc 0.6 O3.
[0125] Fig. 9 1 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig. 9 The C2 yields of samples A3 and A35 at different temperatures are shown in Figure 7 The peak intensity ratios obtained from the XRD patterns are shown.
[0126] [Determination of C2 Yield]
[0127] For samples A3 and A35, the C2 yield at 750°C was determined using the C2 yield determination method described above ( Fig. 9 The yield of C2 at 800 °C ( Fig. 9 In addition, the reduction rate of the C2 yield at 800°C relative to the C2 yield at 750°C was calculated using the measured C2 yield at 750°C and the C2 yield at 800°C ( Fig. 9 “ΔYC2” shown).
[0128] [Derivation of peak intensity ratio]
[0129] For sample A3 and sample A35, analysis based on the powder XRD method was performed to determine the peak intensity ratio between the main phase and the subphase. SmartLab-3kw (manufactured by Rigaku Corporation) was used as an X-ray diffraction apparatus. The measurement conditions based on the powder XRD method are as follows: the scanning range (2θ) is 10°-80°, the step width is 0.02°, the scanning speed is 20° / min, and the measurement is performed using a concentrated optical system. As an X-ray source, CuKα rays were used under the conditions of a tube voltage of 40kV and a tube current of 30mA. For the obtained powder X-ray diffraction spectrum, data analysis was performed using the following method. Smoothing was performed based on the weighted average of 7 smoothing points, and background removal was performed by the Sonnevelt-Visser method with a peak width threshold of 0.1 and an intensity threshold of 0.01. Kα2 removal was implemented using an intensity ratio of 0.5. In the powder X-ray diffraction spectrum using CuKα radiation obtained by the above method, the peak intensity of the perovskite-type oxide constituting the main phase is the largest first peak, and the peak intensity of the composite oxide constituting the subphase is the largest second peak. The ratio of the intensity of the second peak to the intensity of the first peak is calculated ( Fig. 9 “R_peak intensity” shown in the figure).
[0130] like Fig. 9 As shown in FIG. 1 , it was confirmed that the C2 yield at 800°C of sample A35 was higher than that of sample A3, and the decrease rate of the C2 yield at 800°C relative to the C2 yield at 750°C was very low. That is, it was confirmed that, in addition to the main phase composed of the perovskite-type oxide having catalytic activity as a catalyst for the dehydrogenation reaction (BaZr in sample A35), 0.4 Sc 0.6 O3), it also has a subphase composed of a composite oxide (Ba3Sc4O9 in sample A35) formed in the perovskite-type oxide when the above-mentioned perovskite-type oxide is manufactured, thereby improving the heat resistance of the catalyst for dehydrogenation reaction. For example, even at a temperature of 800°C, the decrease in catalytic activity as a catalyst for dehydrogenation reaction is suppressed.
[0131] Fig.10 This is a graph showing the temperature change of the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig.10 This is an explanatory diagram showing the results of measuring the C2 yield of Sample A3 and Sample A35 under the temperature conditions of 650°C, 700°C, 750°C, and 800°C. Fig. 9 Among these results, the measurement results at 750°C and 800°C are shown.
[0132] The complex polymerization method as a method for producing sample A3 is generally known as a method for producing a catalyst having a higher catalytic activity than a solid phase reaction method because it can mix raw materials at a molecular level. Fig.10 It is shown that under the temperature conditions of 700°C and 750°C, the C2 yield of sample A3 is higher than that of sample A35. However, if the operating temperature of the dehydrogenation reaction catalyst rises to 800°C, the catalytic activity (C2 yield) of sample A3 as a dehydrogenation reaction catalyst decreases. In contrast, sample A35 having a subphase prepared by a solid phase reaction method also suppresses the decrease in catalytic activity under the temperature condition of 800°C. It was thus confirmed that the dehydrogenation reaction catalyst of sample A35 prepared by a solid phase reaction method has improved heat resistance. It is believed that the heat treatment temperature when adjusting the catalyst and the presence of the subphase of Ba3Sc4O9 have an effect on the improvement of heat resistance in sample A35.
[0133] Fig.11 FIG. 2 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig.11 This is a diagram for explaining the influence of the presence of a subphase on the performance as a catalyst. Fig.11 In the figure, it is shown that for the main phase BaZr 0.4 Sc 0.6O3 sample A35, samples A36 to A38 with different ratios of zirconium to scandium in the main phase, and sample A39 (Ba3Sc4O9) prepared by solid phase reaction method, the C2 yields at different temperatures ( Fig.11 The reduction rate of the C2 yield at 800°C relative to the C2 yield at 750°C ( Fig.11 "ΔYC2" shown) and the peak intensity ratio obtained from the XRD pattern ( Fig.11 “R_peak intensity” shown in the figure). Fig.11 The C2 yield and peak intensity ratio obtained from the XRD pattern are shown in Fig. 9 The same method as described in the method is used for determination. It should be noted that Fig.11 It also shows Fig. 9 The evaluation results of sample A3 are shown.
[0134] [Production of Samples A36 to A39]
[0135] Samples A36 to A39 were prepared according to the method of preparing sample A35. Fig.11 The types and weighing amounts of the catalyst raw material powders and the heat treatment temperature ("T-treat") of the catalyst powder precursor were adjusted to the composition ratios of the composition formulas of samples A36 to A39 shown in FIG. Fig.11 The temperature shown in the figure is the same as that of sample A35, and powdered catalysts for dehydrogenation reactions as samples A36 to A39 are obtained. Barium carbonate (manufactured by Sakai Chemical Industry Co., Ltd.), zirconium oxide (manufactured by Daiichi Rare Element Chemical Industry Co., Ltd.), and scandium oxide (manufactured by Alfa Aesar) are used as raw material powders. It should be noted that among samples A36 to A39, the number of heat treatments is different from that of sample A35, but the number of heat treatments may also be different.
[0136] like Fig.11As shown, samples A35 to A38 have a higher heat treatment temperature when adjusting the catalyst than sample A3. In addition, it was confirmed that in samples A35 to A38, a subphase was also generated, and the peak intensity ratio (R_peak intensity) of XRD was more than 0.04 relative to the main phase. As shown in sample A39, Ba3Sc4O9 as a subphase did not show degradation of the C2 yield due to temperature rise. On the other hand, it was confirmed that the performance of sample A39 as a catalyst was lower than that of Ba(Zr, Sc)O3-based materials. It was confirmed that in samples A35 to A38, the reduction rate (ΔYC2) of the C2 yield at 800°C (YC2-800) relative to the C2 yield at 750°C (YC2-750) fell within ±1.3%. It can be seen that in samples A35 to A38, relatively high catalytic activity is maintained and heat resistance is improved.
[0137] <Example 2>
[0138] Fig.12 FIG. 1 is a first diagram showing a SEM image of the dehydrogenation reaction catalyst according to the present embodiment. Fig.13 FIG. 2 is a SEM image showing the dehydrogenation reaction catalyst according to the present embodiment. Fig.12 This is the SEM image of sample B1 made by solid phase reaction method. Fig.13 This is a SEM image of sample B12 produced by the complex polymerization method. Here, for two types of dehydrogenation reaction catalyst samples produced by different production methods, changes in surface shape caused by the different production methods were evaluated.
[0139] [Preparation of Sample B1]
[0140] Sample B1 (BaZr 0.8 Y 0.2 O3) was prepared by a solid phase reaction method according to the preparation method of sample A35. Barium carbonate (produced by Sakai Chemical Industry Co., Ltd.), zirconium oxide (produced by Daiichi Kizen Chemical Industry Co., Ltd.), and yttrium oxide (produced by Shin-Etsu Chemical Co., Ltd.) were used as raw material powders. The ratio of the metal elements was such that the composition formula was BaZr 0.8 Y 0.2These raw material powders are weighed in the manner of the composition ratio in O3. Then, jade with a diameter of 5 mm and ethanol are added, and the mixture is mixed for 15 hours using a ball mill. Thereafter, the ethanol component is dispersed, and after obtaining the solid component, it is sieved with a sieve with an opening of 250 μm. Thereafter, it is calcined at 1300°C for 5 hours (calcination process). Jade with a diameter of 5 mm and ethanol are added to the obtained powder and the powder is pulverized again using a ball mill, and mixed for 15 hours (pulverization process). Thereafter, the ethanol component is dispersed, and after obtaining the solid component, it is sieved with a sieve with an opening of 250 μm to obtain a catalyst for dehydrogenation reaction as sample B1.
[0141] [Preparation of sample B12]
[0142] Sample B12 (BaZr 0.8 Y 0.2 O3) was prepared by a complex polymerization method according to the preparation method of sample A1. Barium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), zirconium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), and yttrium nitrate (manufactured by Sigma-Aldrich) were used as raw material powders. The ratio of the metal elements was such that the composition formula was BaZr 0.8 Y 0.2 These raw material powders are weighed in the manner of a composition ratio in O3. Then, for the above raw material powders, a citric acid aqueous solution and propylene glycol are added in a ratio of metal element: citric acid: propylene glycol = 1:3:3 (mol ratio), and stirred and mixed at 80°C for 1 hour. Furthermore, the solution is slowly heated to 300°C to obtain a polymer in which each metal element is dispersed. Furthermore, the obtained polymer is heat-treated at 400°C for 2 hours to carbonize it, and the obtained product is crushed with an agate mortar to obtain a catalyst powder precursor. The obtained catalyst powder precursor is heat-treated at a heat treatment temperature of 1200°C for 6 hours to obtain a powdered catalyst for dehydrogenation reaction as sample B12.
[0143] If you compare Fig.12 The SEM image of sample B1 shown is Fig.13 The SEM image of sample B12 shown in FIG. 0.8 Y 0.2O3), but the surface shape at the micron level is significantly different. Specifically, it was confirmed that the surface structure of sample B1 produced by the solid phase reaction method is finer than that of sample B12 produced by the complex polymerization method. The solid phase reaction method used as the method for producing sample B1 includes a pulverization step based on a ball mill, while the complex polymerization method used as the method for producing sample B12 does not include a pulverization step. Therefore, it is believed that Fig.12 and Fig.13 As shown, the surface shape and the size of the granular blocks forming the surface shape are different.
[0144] Fig.14 This is a diagram showing the specific surface area of the dehydrogenation reaction catalyst according to the present embodiment. Fig.14 This is a diagram for explaining the influence of the composition and production method of the dehydrogenation reaction catalyst on the specific surface area of the dehydrogenation reaction catalyst. Fig.14 , the results of comparing the specific surface areas of a plurality of samples B1 to B5 having different compositions produced by the solid phase reaction method and a sample B12 produced by the complex polymerization method are shown.
[0145] [Preparation of Samples B2 to B5]
[0146] Samples B2 to B5 were prepared by the method according to the method for preparing sample B1. Fig.14 The type and weighing amount of the raw material powder of the catalyst are adjusted in the manner of the composition ratio of the composition formula of samples B2 to B5 shown in the figure. In addition, in the same manner as sample B1, powdered catalysts for dehydrogenation reactions as samples B2 to B5 are obtained. It should be noted that samples B3 to B5 can be obtained by repeating the calcination process (heat treatment temperature 1300°C, calcination time 5 hours) and the pulverization process based on a ball mill to obtain a powdered catalyst for dehydrogenation reactions. Barium carbonate (manufactured by Sakai Chemical Industry Co., Ltd.), zirconium oxide (manufactured by Daiichi Rare Element Chemical Industry Co., Ltd.), yttrium oxide (manufactured by Shin-Etsu Chemical Co., Ltd.), and scandium oxide (manufactured by Alfa Aesar) are used as raw material powders.
[0147] [Measurement of specific surface area]
[0148] For samples B1 to B5 and B12, the specific surface area was measured using a specific surface area measuring device (Macsorb HM model-1208 manufactured by MOUNTECH Co., Ltd.) according to the BET flow single-point method (He:N2=7:3). Specifically, the prepared particles of samples B1 to B5 and B12 were filled into a test tube, degassed at 200°C for 60 minutes, and then cooled together with the test tube. After cooling, the amount of gas physically adsorbed on the surface of the particles filled in the test tube was measured using the change in gas concentration, and the specific surface area of the particles ( Fig.14 The “Specific surfaces are” shown in a).
[0149] like Fig.14 As shown, the comparison of the specific surface area of sample B1 with that of sample B12 confirmed that Fig.12 and Fig.13 As shown, the surface shape has changed, and as a result, the specific surface area of the dehydrogenation reaction catalyst has changed. Specifically, it was confirmed that the specific surface area of sample B1 is more than twice the specific surface area of sample B12. It is expected that the reactivity with the dehydrogenation reaction catalyst per unit weight will increase. Among samples B1 to B5, the specific surface area measured by the BET flow 1-point method is 10m 2 / g or more. For example, the comparison between sample B1 and sample B3 confirmed that among the elements contained in the B site, the specific surface area of scandium is larger than that of yttrium. The comparison between sample B1 and sample B2, or samples B3 to B6 confirmed that the specific surface area increases as the ratio of zirconium increases.
[0150] Fig.15 FIG1 is a first diagram showing an XPS spectrum of the dehydrogenation reaction catalyst according to the present embodiment. Fig.15 , spectra of O1s orbital included in the photoelectron spectra obtained by X-ray photoelectron spectroscopy are shown for Sample B1 and Sample B12, respectively.
[0151] [Measurement of the spectrum of O1s orbital]
[0152] For sample B1 and sample B12, spectra of the O1s orbital were obtained by X-ray photoelectron spectroscopy (XPS). Specifically, for the cross section of the powder compact made from particles of sample B1 or sample B12, an XPS spectrum within a range of 100 μmφ was obtained using monochromatized AlKα rays as an X-ray source with a path energy of 140 eV.
[0153] Fig.15In the O1s orbital spectra of each of the samples B1 and B12, two peaks were confirmed. Of the two peaks that appeared in the O1s orbital spectra, the Binding Energy was around 532 eV ( Fig.15 The peak in the region Aao shown in FIG. 1 is derived from the adsorbed oxygen species. In addition, the Binding Energy is around 528 eV ( Fig.15 The peak in the area A1o shown in the figure is a peak derived from the lattice oxygen substance. It was confirmed that, for sample B1 and sample B12, when comparing the area of the convex portion containing the peak derived from the adsorbed oxygen substance and the area of the convex portion containing the peak derived from the lattice oxygen substance, respectively, in sample B12, the area of the convex portion containing the peak derived from the lattice oxygen substance is larger than the area of the convex portion containing the peak derived from the adsorbed oxygen substance, while on the other hand, in sample B1, the area of the convex portion containing the peak derived from the adsorbed oxygen substance is larger than the area of the convex portion containing the peak derived from the lattice oxygen substance. In sample B1, the solid phase reaction method as the preparation method of sample B1 includes a pulverization step based on a ball mill, so it is believed that a convex portion is formed by mechanical force. Fig.12 On the other hand, in sample B12, the complex polymerization method used as the preparation method of sample B12 does not include a step of applying a mechanical force such as the pulverization step of the solid phase reaction method. Fig.13 As shown in the SEM image of , it does not have a surface with the shape of sample B1. Thus, in sample B1 and sample B12, the surface shape is different depending on the presence or absence of the pulverization process, so it is believed that the magnitude relationship between the amount of adsorbed oxygen species and the amount of lattice oxygen species has changed. It should be noted that the specific comparison results of the area of the convex portion containing the peak in the XPS spectrum will be described later.
[0154] Fig.16 FIG2 is a second diagram showing the XPS spectrum of the dehydrogenation reaction catalyst according to the present embodiment. Fig.16 , for Sample B1, Sample B2, and Sample B13, spectra of O1s orbital included in photoelectron spectra obtained by X-ray photoelectron spectroscopy are shown. Fig.16 The samples B1, B2 and B13 shown in the figure all have the composition formula of Ba(Zr 1-x Y x ) 3-δ The dehydrogenation reaction catalysts shown are different in value of x (sample B1: x=0.2, sample B2: x=0.4, sample B13: x=0).
[0155] [Preparation of sample B13]
[0156] Sample B13 (BaZrO3) was prepared by a solid phase reaction method according to the preparation method of sample B1. Specifically, the type and weighing amount of the raw material powder of the catalyst were adjusted in a manner to obtain a composition ratio of the composition formula of sample B13. In the same manner as sample B1, a powdered catalyst for dehydrogenation reaction as sample B13 was obtained. Barium carbonate (manufactured by Sakai Chemical Industry Co., Ltd.) and zirconium oxide (manufactured by Daiichi Rare Element Chemical Industry Co., Ltd.) were used as raw material powders.
[0157] like Fig.16 As shown, the composition formula is Ba(Zr 1-x Y x ) 3-δ The larger the value of x of the dehydrogenation reaction catalyst shown, the more likely it is to have oxygen defects due to charge compensation. Fig.16 Among the three samples shown, it was confirmed that in sample B2 where x was greater than sample B1, the ratio of the area of the convex portion containing the peak derived from the adsorbed oxygen substance to the area of the convex portion containing the peak derived from the lattice oxygen substance was greater than that of sample B1, and in sample B13 where x was less than that of sample B1, the ratio of the area of the convex portion containing the peak derived from the adsorbed oxygen substance to the area of the convex portion containing the peak derived from the lattice oxygen substance was smaller than that of sample B1. That is, it was confirmed that the larger the value of x, the greater the ratio of the area of the convex portion containing the peak derived from the adsorbed oxygen substance to the area of the convex portion containing the peak derived from the lattice oxygen substance. Composition formula Ba(Zr 1-x Y x ) 3-δ In the dehydrogenation reaction catalyst shown, it is believed that increasing the value of x increases the amount of oxygen defects and increases the coordination unsaturation of the catalyst surface near the oxygen defects. This allows more oxygen to be adsorbed, and therefore it is believed that the amount of oxygen-adsorbing substances increases.
[0158] Fig.17 FIG3 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig.17 This is a diagram for explaining the relationship between the composition of the dehydrogenation reaction catalyst and the C2 yield. Fig.17 In the figure, for samples B1 to B11 prepared by the solid phase reaction method, sample B13 and sample B12 prepared by the complex polymerization method, the ratio of the peak area originating from the adsorbed oxygen substance to the peak area originating from the lattice oxygen substance in the spectrum of the O1s orbital obtained by XPS measurement (hereinafter referred to as "XPS ratio") and the C2 yield at 700°C are shown respectively.
[0159] [Preparation of Samples B6 to B11]
[0160] Samples B6 to B11 were prepared by the method according to the method for preparing sample B1. Fig.17 The type and weighing amount of the raw material powder of the catalyst are adjusted in the manner of the composition ratio of the composition formula of samples B6 to B11 shown. In the same manner as sample B1, powdered catalysts for dehydrogenation reactions as samples B6 to B11 are obtained in the same manner as sample B1. In samples B6 and B7, the calcination process and the pulverization process based on a ball mill are repeated in the same manner as sample B5, thereby obtaining a powdered catalyst for dehydrogenation reactions. In samples B8 to B11, the heat treatment temperature in the calcination process is changed within the range of 1300°C to 1500°C in such a manner that the proportion of the target object becomes higher. For example, in sample B10, it is 1400°C, and in sample B11, it is 1350°C. In this way, the heat treatment temperature in the calcination process when making the sample can be changed in such a manner that the proportion of the target object becomes higher. As raw material powders, barium carbonate (manufactured by Sakai Chemical Industry Co., Ltd.), zirconium oxide (manufactured by Daiichi Kizenso Kagaku Kogyo Co., Ltd.), scandium oxide (manufactured by Alfa Aesar Co., Ltd.), lanthanum hydroxide (manufactured by Shin-Etsu Chemical Co., Ltd.), and strontium carbonate (manufactured by Kojundo Kagaku Laboratory Co., Ltd.) were used.
[0161] [Determination of XPS ratio]
[0162] Fig.18 : is a diagram for explaining a method for calculating the XPS ratio. When the XPS ratio is calculated, Fig.18 As shown, the spectrum Sp1 of the O1s orbital obtained by XPS measurement is divided into the first curve Cr1 and the second curve Cr2 by peak separation fitting processing, wherein the first curve Cr1 has a first peak corresponding to the maximum value in the range Ra1 of 525-530 eV of Binding Energy, and the second curve Cr2 has a second peak corresponding to the maximum value in the range Ra2 of 530-535 eV of Bonding Energy. The baseline Ba1 that becomes the basis of the first curve Cr1 is set, and the area of the portion surrounded by the first curve Cr1 and the baseline Ba1 is set as the first peak area Slo derived from the lattice oxygen substance. The baseline Ba2 that becomes the basis of the second curve Cr2 is set, and the area of the portion surrounded by the second curve Cr2 and the baseline Ba2 is set as the second peak area Sa derived from the adsorbed oxygen substance. Therefore, the XPS ratio is derived based on Sao / Slo. Fig.17 In the XPS ratio, Sao / Slo is expressed. The first peak area Slo corresponds to the "area of the convex portion including the first peak" in the claims. The second peak area Sao corresponds to the "area of the convex portion including the second peak" in the claims.
[0163] [Determination of C2 Yield]
[0164] The determination of the C2 yield of each of the samples B1 to B13 was carried out in the same manner as the determination of the C2 yield of the samples A1 to A34 described above, using a fixed bed flow reactor. Specifically, 0.1 g of each of the samples B1 to B13 was weighed and placed in a fixed bed flow reactor, and a mixed gas of methane, oxygen and nitrogen was heated to a predetermined temperature, with a flow ratio of CH4:O2:N2=3.8:1:4, and the mixture was heated at 1 atmosphere and 45 cm 3 / min flow, and carry out catalytic activity test. Fig.17 The "YC2-700" shown here indicates the results obtained in a state where each sample was heated to 700°C.
[0165] like Fig.17 As shown, the XPS ratio ( Fig.17 If the "Sao / Slo" shown in the figure is large, it is confirmed that the C2 yield at 700°C ( Fig.17 In particular, in samples B1 to B11 in which the XPS ratio, i.e., the ratio of the second peak area to the first peak area is greater than 1, a tendency for the C2 yield at 700°C to further increase was confirmed. In the dehydrogenation reaction catalyst, the oxygen-adsorbed substance exists in an activated state, and therefore, the dehydrogenation reactivity of the dehydrogenation reaction catalyst becomes higher. A high XPS ratio, which represents the ratio of the first peak area derived from the oxygen-adsorbed substance to the second peak area derived from the lattice oxygen substance, indicates that a relatively large amount of oxygen-adsorbed substance is present, and therefore, if the XPS ratio is high, the dehydrogenation reactivity of the dehydrogenation reaction catalyst becomes higher.
[0166] Depend on Fig.17 The results shown indicate that in order to improve the XPS ratio in the dehydrogenation reaction catalyst, (a) the method for preparing the dehydrogenation reaction catalyst must satisfy two factors: a pulverization step based on a solid phase reaction method and (b) the introduction of oxygen defects based on element substitution. In the dehydrogenation reaction catalyst, the XPS ratio can be improved by the synergistic effect of these two factors (a) and (b). Fig.17 Among the multiple samples shown, samples B1 to B11 all satisfy the two factors (a) and (b). On the other hand, sample B12 satisfies factor (b) but does not satisfy factor (a). Sample B13 satisfies factor (a) but does not satisfy factor (b).
[0167] Fig.19 FIG. 4 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig.19 It is a graph for explaining the relationship between the calculated XPS ratio and the C2 yield. Fig.19 In the graph, the horizontal axis is the XPS ratio (Sao / Slo) and the vertical axis is the C2 yield (YC2-700) at 700°C. Fig.17 The values of the 13 samples B1 to B13 are shown in Table 1. Fig.19 As shown, it was confirmed that the C2 yield at 700° C. increased when the XPS ratio became higher than 1. This is considered to be because the amount of activated oxygen-adsorbing species on the surface of the dehydrogenation reaction catalyst increased, thereby promoting the dehydrogenation reaction.
[0168] Fig. 20 FIG5 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig. 20 This is a diagram for explaining the temperature dependence of the C2 yield of the dehydrogenation reaction catalyst. Fig. 20 In, for Fig.17 Samples B4 to B7 among the samples B1 to B13 shown in the figure respectively show the C2 yield (YC2-750) at 750° C. Samples B4 to B7 are so-called Ba(Zr, Sc)O3-based materials.
[0169] [Determination of C2 Yield]
[0170] The measurement of the C2 yield at 750° C. of each of Samples B4 to B7 was performed using a fixed bed flow reactor in the same manner as the measurement of the C2 yield at 700° C. of Samples B1 to B13 described above. Fig. 20 The "YC2-750" shown here indicates the results obtained by heating each sample to 750°C.
[0171] like Fig. 20 As shown, it was confirmed that the C2 yields at 750° C. of Samples B4 to B7 were all higher than the C2 yields at 700° C. Therefore, for the dehydrogenation reaction catalyst of the perovskite-type oxide of the Ba(Zr, Sc)O3-based material produced by the solid phase reaction method, it was confirmed that there was no degradation in the performance of the dehydrogenation reaction catalyst due to the temperature increase from 700° C. to 750° C.
[0172] According to the dehydrogenation reaction catalyst of this embodiment configured as above, it has the general formula (A 1-x A' x )(Zr 1-y- z B y B' z ) 3-δA main phase composed of a perovskite-type oxide as shown; and a subphase composed of at least one of the three composite oxides represented by the general formula AB'2O4, A2B'2O5, and A3B'4O9. Here, in the main phase, A is at least one element selected from alkaline earth metals, A' is at least one element selected from lanthanum (La) and yttrium (Y), B is at least one element selected from titanium (Ti) and cerium (Ce), and B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and neodymium (Nd), satisfying 0≤x≤0.4, 0.3≤(1-z)≤1, 0≤y, 0<(1-yz), δ represents the oxygen deficiency, and A and B' in the subphase are elements common to A and B' constituting the perovskite-type oxide. Thus, the heat resistance of the catalyst for dehydrogenation reaction can be improved.
[0173] In addition, according to the dehydrogenation reaction catalyst of this embodiment, A is barium (Ba), B' is scandium (Sc), and the subphase is composed of at least one barium scandate among the three composite oxides of BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9. Thus, the heat resistance of the dehydrogenation reaction catalyst can be further improved.
[0174] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, the subphase is composed of Ba3Sc4O9. This can further improve the heat resistance of the dehydrogenation reaction catalyst.
[0175] In addition, according to the dehydrogenation reaction catalyst of this embodiment, the main phase is BaZr 1-z Sc z O 3-δ (wherein 0.1≤z≤0.7) This can further improve the catalytic activity as a dehydrogenation reaction catalyst.
[0176] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, the ratio of the intensity of the second peak to the intensity of the first peak in the powder X-ray diffraction spectrum using CuKα rays is 0.04 or more. This can further improve the heat resistance of the dehydrogenation reaction catalyst.
[0177] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, the subphase is composed of any one of the composite oxides of BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9. This can further improve the heat resistance of the dehydrogenation reaction catalyst.
[0178] In addition, the catalyst for dehydrogenation reaction of the present embodiment can be used as a methane oxidative coupling catalyst for producing hydrocarbons having a carbon number of 2 or more from methane. This can improve the heat resistance of the methane oxidative coupling catalyst.
[0179] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, for the spectrum of the O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy, the ratio of the second peak area to the first peak area is greater than 1. As a result, the oxygen-adsorbing species becomes easy to adsorb on the surface of the dehydrogenation reaction catalyst, and thus the catalytic activity as the dehydrogenation reaction catalyst can be improved.
[0180] In addition, the dehydrogenation reaction catalyst of the present embodiment has oxygen defects. This can increase the amount of oxygen-adsorbed species on the surface of the dehydrogenation reaction catalyst, and thus can further improve the catalytic activity of the dehydrogenation reaction catalyst.
[0181] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, the main phase of the catalyst is a perovskite structure, thereby further improving the catalytic activity of the dehydrogenation reaction catalyst.
[0182] In addition, according to the catalyst for dehydrogenation reaction of this embodiment, the specific surface area measured by the BET method is 10 m 2 This can increase the amount of oxygen-adsorbed species on the surface of the dehydrogenation reaction catalyst, and thus can further improve the catalytic activity of the dehydrogenation reaction catalyst.
[0183] In addition, the catalyst for dehydrogenation reaction of the present embodiment can be used as a methane oxidative coupling catalyst for producing hydrocarbons having a carbon number of 2 or more from methane. This can improve the catalytic performance of the methane oxidative coupling catalyst.
[0184] <Second Embodiment>
[0185] The dehydrogenation reaction catalyst of the second embodiment has a different composition formula from that of the dehydrogenation reaction catalyst of the first embodiment.
[0186] [Dehydrogenation reaction catalyst]
[0187] The dehydrogenation reaction catalyst of the present embodiment is a composite oxide having a perovskite-type oxide crystal structure represented by the general formula (26) shown below.
[0188] (La 1-x M1 x )M2O 3-δ …(26)
[0189] In the above formula (26), M1 is at least one element selected from alkaline earth metals, M2 is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and gallium (Ga), and δ represents the oxygen deficiency amount, satisfying 0≤x≤0.6.
[0190] In the catalyst for dehydrogenation reaction of the present embodiment, the perovskite-type oxide of formula (26) has catalytic activity as a catalyst for dehydrogenation reaction. The perovskite-type oxide of formula (26) contains lanthanum (La) and at least one element M1 selected from alkaline earth metals at the so-called A site of the perovskite structure. The element M1 is preferably selected from strontium (Sr) or barium (Ba). In addition, the perovskite-type oxide of formula (26) contains an M2 element at the so-called B site of the perovskite structure. As the M2 element, at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and gallium (Ga) is included.
[0191] In the perovskite-type oxide of formula (26), x satisfies the following formula (27). Thus, the dehydrogenation reaction catalyst of the present embodiment has a high catalytic activity as a dehydrogenation reaction catalyst that promotes the dehydrogenation reaction.
[0192] 0≤x≤0.6 … (27)
[0193] The dehydrogenation reaction catalyst of this embodiment configured as above has a perovskite oxide crystal structure represented by formula (26), thereby improving the catalytic activity of the dehydrogenation reaction catalyst, which promotes the dehydrogenation reaction at a relatively low temperature of about 650°C to 700°C, for example.
[0194] The catalyst for dehydrogenation reaction of the present embodiment can promote various dehydrogenation reactions in which hydrogen is separated from a compound. As a dehydrogenation reaction, for example, the oxidative coupling of methane (OCM) reaction for producing hydrocarbons having a carbon number of 2 or more from methane can be cited. Therefore, the catalyst for dehydrogenation reaction of the present embodiment can also be used as a methane oxidative coupling catalyst. In addition, various reactions in which hydrogen is generated by dehydrogenation reactions of various hydrocarbon compounds including hydrocarbons and alcohols can be cited. Specifically, steam reforming reactions in which hydrogen is generated from hydrocarbon compounds and water vapor, partial oxidation reactions in which hydrogen is generated from hydrocarbon compounds, conversion reactions in which carbon monoxide and water vapor generated together with hydrogen in partial oxidation reactions are used to produce carbon dioxide and hydrogen, etc. can be cited.
[0195] Figure 2 and Figure 3This is an explanatory diagram showing an example of a methane oxidative coupling reaction performed on a methane oxidative coupling catalyst in the case where the catalyst for dehydrogenation reaction of the present embodiment is a methane oxidative coupling catalyst as an example of a reaction including a dehydrogenation reaction. When the dehydrogenation reaction in which hydrogen is separated from a compound proceeds, the covalent bonds between atoms such as carbon constituting the compound and hydrogen atoms are usually cut. The catalyst for dehydrogenation reaction of the present embodiment is believed to exhibit high activity in promoting dehydrogenation reactions by promoting such reactions. In the methane oxidative coupling reaction, the reaction of generating methyl radicals from methane shown in the following formula (5) proceeds, and further, the reactions of the following formulas (6) and (7) (refer to Figure 2 ), the following reactions of formula (8) and formula (9) (refer to Figure 3 ) is carried out, and it is believed that C2 hydrocarbons such as ethylene are produced. The overall reaction of producing ethylene by methane oxidative coupling reaction is represented by the following formula (10).
[0196] CH4 → ·CH3+H + +e - … (5)
[0197] 2·CH3+1 / 2O2 → C2H4+H2O … (6)
[0198] 1 / 2O2+2H + +2e - → H2O … (7)
[0199] 2. CH3 → C2H6 → C2H4+2H + +2e - … (8)
[0200] O2+4H + +4e - →2H2O…(9)
[0201] 2CH4+O2 → C2H4+2H2O … (10)
[0202] Here, the bonding energy of the covalent bond between the carbon atom and the hydrogen atom in methane is 104kcal / mol, which is an extremely stable bond. Therefore, in the methane oxidative coupling reaction, it is generally believed that the reaction (reaction of formula (5)) in which methane with a stable covalent bond is dehydrogenated to produce methyl radicals as described above becomes the rate-determining process. The catalyst for the dehydrogenation reaction of the present embodiment has a high activity in promoting the reaction accompanied by the severance of the covalent bond in hydrogen such as the reaction of generating methyl radicals from methane as described above, and therefore it is believed that it can widely promote dehydrogenation reactions such as the oxidative coupling reaction of methane accompanied by the severance of the covalent bond in hydrogen. Furthermore, the catalyst for the dehydrogenation reaction of the present embodiment is a perovskite-type oxide, and therefore, it is a proton conductor that can protonate and move the hydrogen of the molecule containing hydrogen. Therefore, it is believed that the activity of promoting the reaction accompanied by the severance of the covalent bond containing hydrogen is high, and it can widely promote dehydrogenation reactions such as the oxidative coupling reaction of methane accompanied by the severance of the covalent bond containing hydrogen.
[0203] Figure 2 and Figure 3 In the above, the site where the reaction of formula (5) from methane to methyl radical proceeds is represented as an "oxidation site". Figure 2 and Figure 3 In the figure, the state in which the reaction of formula (6) or formula (8) in which ethylene is further generated from a methyl radical at the oxidation site is shown. Figure 2 and Figure 3 In the reaction of formula (7) or formula (9) in which the protons and electrons generated together with the methyl radical in formula (5) are used to generate water, the site is represented as a "reduction site". In this way, when the reaction of the dehydrogenation reaction in the catalyst for dehydrogenation reaction of the present embodiment is carried out, it is usually accompanied by the acceptance of protons and electrons. Therefore, in order to improve the catalytic activity, the catalyst for dehydrogenation reaction is expected to have high proton conductivity and electron conductivity (including hole conductivity) in addition to promoting the high activity of the reaction of formula (5) belonging to the rate-controlling process. Specifically, it is expected that the proton conductivity, the proton migration number, or the electron conductivity (including the hole migration number) and the electron migration number (including the hole migration number) are higher. Moreover, as a whole catalyst for dehydrogenation reaction, it is expected that the total of the proton conductivity and the electron conductivity (including the hole conductivity), that is, the total conductivity, is also higher.
[0204] [Other dehydrogenation reactions]
[0205] Figure 4 The diagram shows chemical formulas of various dehydrogenation reactions that the dehydrogenation reaction catalyst of the present embodiment can promote. The dehydrogenation reaction catalyst of the present embodiment can promote various reactions depending on the raw materials (reactants) used. Figure 4In formulas (11) to (22), a reaction is shown in which reactants containing at least one of methane and methane derivatives (hereinafter also referred to as "methanes") are bonded. Such a reaction is also referred to as a "methane oxidative coupling reaction". Furthermore, the dehydrogenation reaction catalyst of this embodiment that promotes the methane oxidative coupling reaction is also referred to as a "methane oxidative coupling catalyst". It should be noted that Figure 4 In the formulae (13) to (22), A and B contained in the methane derivative represent atoms or atomic groups that are substituents replacing hydrogen in the methane hydrocarbon molecule, and n is an integer of 2 or more. Figure 4 The methane derivatives shown are obtained by replacing one or two hydrogen atoms contained in the methane hydrocarbon molecule with the above-mentioned substituents. When one molecule has a substituent A and a substituent B, A and B may be the same substituent or different substituents. Examples of the substituents represented by A or B include halogen elements, hydroxyl groups (-OH), and phenyl groups (-C6H5).
[0206] Figure 4 In the above formula, (11) represents the reaction of producing ethylene from methane, similarly to (10). (12) represents the reaction of producing polyethylene by further polymerization. Unlike (10), formulas (11) to (22) only show the changes of methane and methane derivatives in the molecules involved in the reaction.
[0207] Formulas (11) and (12) represent reactions using methane as a reactant. Formulas (13) and (14) represent reactions using a methane derivative represented by BACH2 as a reactant. Formulas (15) and (16) represent reactions using a methane derivative represented by ACH3 as a reactant. Formulas (17) and (18) represent reactions using a methane derivative represented by ACH3 and methane as reactants. Formulas (19) and (20) represent reactions using a methane derivative represented by ACH3 and a methane derivative represented by CA2H2 as reactants. Formulas (21) and (22) represent reactions using a methane derivative represented by CABH2 and methane as reactants.
[0208] In addition, formula (11), formula (13), formula (15), formula (17), formula (19) and formula (21) represent reactions for producing hydrocarbons (ethylene) or ethylene derivatives (hereinafter, also referred to as "C2 hydrocarbons") having a carbon number of 2 using reactants selected from hydrocarbons having a carbon number of 1 (methane) and methane derivatives (hereinafter, also referred to as "C1 hydrocarbons"). Formula (12), formula (14), formula (16), formula (18), formula (20) and formula (22) represent reactions for producing polymers using reactants selected from C1 hydrocarbons. When producing polymers, after C2 hydrocarbons are produced from C1 hydrocarbons, these C2 hydrocarbons may be further polymerized with each other, or C1 hydrocarbons may be polymerized sequentially at the ends of the molecules to form a polymer, or both reactions may be performed.
[0209] right Figure 4 When the reaction shown is further specifically described, for example, in formula (14), if both A and B of the substituents are fluorine atoms (F), polytetrafluoroethylene (PTFE) is obtained as a product. In formula (18), if substituent A is a chlorine atom (Cl), polyvinyl chloride (PVC) is obtained as a product, if substituent A is a hydroxyl group (-OH), polyvinyl alcohol (PVOH) is obtained as a product, and if substituent A is a phenyl group (-C6H5), polystyrene (PS) is obtained as a product. In formula (22), if both A and B of the substituents are fluorine atoms (F), polyvinylidene fluoride (PVDF) is obtained as a product, and if both A and B of the substituents are chlorine atoms (Cl), polyvinylidene chloride (PVDC) is obtained as a product. In addition, in formula (22), if substituent A is a methyl group (-CH3) and substituent B is a methoxycarbonyl group (-COOCH3), polymethyl methacrylate (PMMA) is obtained as a product.
[0210] Figure 4 In the embodiment, a methane oxidative coupling reaction is shown, but the dehydrogenation reaction catalyst of the present embodiment can also be used to promote dehydrogenation reactions other than methane oxidative coupling reactions. As a dehydrogenation reaction promoted by the dehydrogenation reaction catalyst of the present embodiment, for example, a reaction in which reactants containing at least one of alkanes and alkane derivatives (hereinafter also referred to as "alkanes") are bonded can be cited. Such a reaction is also referred to as an "alkane oxidative coupling reaction" together with the methane oxidative coupling reaction described above. The dehydrogenation reaction catalyst of the present embodiment that promotes the alkane oxidative coupling reaction is also referred to as an "alkane oxidative coupling catalyst". The carbon number of the alkanes of the reactants of the alkane oxidative coupling reaction promoted by the dehydrogenation reaction catalyst of the present embodiment can be set to 1 to 10, preferably 1 to 5, and more preferably 1 or 2. It should be noted that the alkane derivative provided for the alkane oxidative coupling reaction is formed by replacing the hydrogen contained in the alkane molecule with the substituent, but has a covalent bond between the carbon atom and the hydrogen atom that is the object of dehydrogenation.
[0211] The dehydrogenation reaction catalyst of this embodiment can also be used to promote hydrogen reactions other than alkane oxidative coupling reactions. Other dehydrogenation reactions promoted by the dehydrogenation reaction catalyst of this embodiment include, for example: Figure 4The dehydrogenation reaction of alkanes exemplified in formula (23), and the dehydrogenation reaction of alcohols or alcohol derivatives (hereinafter also referred to as "alcohols") exemplified in formulas (24) and (25). In formulas (23) to (25), A and B represent hydrogen, or, as in formulas (13) to (22), represent atoms or atomic groups that are substituents that replace hydrogen. Formula (23) represents a reaction of generating olefins or olefin derivatives from alkanes. Formula (24) represents a reaction of generating aldehydes from alcohols, and formula (25) represents a reaction of generating ketones from alcohols. In this way, the dehydrogenation reaction catalyst of this embodiment can be used as a catalyst that promotes various dehydrogenation reactions.
[0212] [Method for producing a dehydrogenation reaction catalyst]
[0213] The catalyst for dehydrogenation reaction of the present embodiment can be prepared, for example, by a solid phase reaction method. Specifically, a solvent such as ethanol is used to mix powders of metal oxides, metal carbonates, etc., which are raw materials of the perovskite-type oxide shown in formula (26), in a ball mill, etc., and then the solvent is removed by drying and sintering is performed. At this time, sintering is performed at a relatively high temperature of about 1300-1600°C, so that a composite oxide shown in formula (26) can be obtained. It should be noted that, as a method for preparing composite oxides, in addition to the solid phase reaction method, various methods such as complex polymerization method, coprecipitation method, sol-gel method, etc. are also known, and even these methods can be used to prepare.
[0214] Fig.21 FIG6 is a diagram showing the C2 yield of the dehydrogenation reaction catalyst according to the present embodiment. Fig.21 This is a diagram for explaining the results of preparing 12 kinds of composite oxides of samples C1 to C12 and investigating their performance. Among samples C1 to C12, samples C1 to C8 are perovskite-type oxides that satisfy the above-mentioned formula (26), as well as the conditions of the element type at the A site, the ratio of the elements in the A site, the element type at the B site, and the amount of oxygen deficiency. Samples 9 to C12 are composite oxides that do not satisfy the formula (26), as well as at least any of the element type at the A site, the ratio of the elements in the A site, the element type at the B site, and the amount of oxygen deficiency. Fig.21 In the perovskite oxides of samples C1 to C12, the proportion of lanthanum in the A site is represented as "P-La". It should be noted that in the following descriptions and the descriptions in the figures, the number of oxygen atoms in the formula is sometimes simplified to "O3", but these descriptions are different from "O 3-δ " has the same meaning, and δ is not strictly represented as 0. The composition, production method, evaluation method and performance evaluation results of each sample are described below. Here, the performance as a catalyst for dehydrogenation reaction is evaluated as a methane oxidative coupling catalyst.
[0215] [Preparation of Sample C1]
[0216] The catalyst of sample C1 (La 0.9 Sr 0.1 ScO3) is produced by a solid phase reaction method. Lanthanum hydroxide (produced by Shin-Etsu Chemical Co., Ltd.), strontium carbonate (produced by High Purity Science Laboratory Co., Ltd.) and scandium oxide (produced by Alfa Aesar) are used as raw material powders. The ratio of the metal elements is La 0.9 Sr 0.1 These raw material powders were weighed in the manner of the composition ratio of ScO3. Then, jade with a diameter of 5 mm and ethanol were added, and the mixture was mixed for 15 hours using a ball mill. After that, the ethanol component was dispersed, and after obtaining the solid component, it was sieved with a sieve with an opening of 250 μm. After that, it was calcined at 1300°C for 5 hours. Jade with a diameter of 5 mm and ethanol were added to the obtained powder and the powder was pulverized again using a ball mill, mixed for 15 hours, and the ethanol component was dispersed, and after obtaining the solid component, it was sieved with a sieve with an opening of 250 μm, thereby obtaining a catalyst for dehydrogenation reaction as sample C1.
[0217] [Preparation of Samples C2 to C9]
[0218] To become Fig.21 The type and weighing amount of the raw material powder of the catalyst are adjusted in the manner of the composition ratio of the composition formula of samples C2 to C9 shown in the figure. In the same manner as sample C1, powdered catalysts for dehydrogenation reactions as samples C2 to C9 are obtained. In samples C3 and C4, the heat treatment temperature in the calcination process is changed within the range of 1300°C to 1500°C in such a manner that the proportion of the target substance becomes higher. For example, in sample C3, it is 1400°C, and in sample C4, it is 1350°C. In this way, the heat treatment temperature in the calcination process when the sample is produced can be changed in such a manner that the proportion of the target substance becomes higher. In the catalyst for dehydrogenation reaction, in order to add lanthanum, strontium, scandium, barium, aluminum, gallium and zirconium as constituent elements, lanthanum hydroxide (manufactured by Shin-Etsu Chemical Co., Ltd.), strontium carbonate (manufactured by Kojundo Science Laboratory Co., Ltd.), scandium oxide (manufactured by Alfa Aesar Co., Ltd.), barium carbonate (manufactured by Sakai Chemical Industry Co., Ltd.), aluminum oxide (Sumitomo Chemical Co., Ltd.), gallium oxide (Kishida Chemical Co., Ltd.) and zirconium oxide (manufactured by Dai-ichi Kizen Chemical Co., Ltd.) were used as raw material powders.
[0219] [Preparation of sample C10]
[0220] The catalyst (SrTiO3) of sample C10 was prepared by complex polymerization. Strontium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation) and titanium tetraisopropoxide (manufactured by Kojun Chemical Research Institute Co., Ltd.) were used as raw material powders. These raw material powders were weighed in such a way that the ratio of the metal elements became the composition ratio in the composition formula SrTiO3. Then, for the above raw material powders, citric acid aqueous solution and propylene glycol were added in such a way that the ratio of metal element: citric acid: propylene glycol = 1:3:3 (mol ratio), and stirred and mixed at 80°C for 1 hour. Furthermore, the solution was slowly heated to 300°C to obtain a polymer in which each metal element was dispersed. Furthermore, the obtained polymer was heat-treated at 400°C for 2 hours to carbonize it, and the obtained was crushed with an agate mortar to obtain a catalyst powder precursor. The obtained catalyst powder precursor was heat-treated at a heat treatment temperature of 1200°C for 6 hours to obtain a powdered catalyst for dehydrogenation reaction as sample C10.
[0221] [Preparation of Samples C11 to C13]
[0222] To become Fig.21 Powdered catalysts for dehydrogenation reactions of samples C11 to C13 were obtained in the same manner as sample C10 except that the type and the weighed amount of the raw material powder of the catalyst were adjusted in the manner of the composition ratio of the composition formula of samples C11 to C13 shown in FIG. In order to add strontium, lanthanum, titanium, barium, zirconium, and yttrium as constituent elements, the raw material powders used were strontium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), lanthanum nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), titanium tetraisopropoxide (manufactured by Kojun Chemical Research Institute Co., Ltd.), barium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), zirconium nitrate (manufactured by FUJIFILM Wako Chemicals Corporation), and yttrium nitrate (manufactured by Sigma-Aldrich Corporation).
[0223] [Determination of C2 Yield]
[0224] 0.1 g of each sample C1 to sample C13 was weighed and placed in a fixed bed flow reactor. A mixed gas of methane, oxygen and nitrogen was heated to 750°C with a flow ratio of CH4:O2:N2=3.8:1:4 and heated at 1 atm and 45 cm 3 / min flow, and conduct catalytic activity test. This catalytic activity test was conducted in a state where each sample was heated to 650°C. The composition analysis of the gas input into the device and the gas discharged was conducted using a micro gas chromatograph (Agilent Technologies, Inc., 3000A). Using the results of the composition analysis, the C2 yield at 650°C was calculated ( Fig.21 "YC2-650" shown).
[0225] like Fig.21 As shown, it was confirmed that among samples C1 to C13, samples C1 to C8, which are composite oxides containing a relatively large amount of lanthanum at the A site, had a larger C2 yield (YC2-650) at 650° C. than samples C9 to C13, which are composite oxides not containing a large amount of lanthanum at the A site. It was confirmed that the composite oxide containing a large amount of lanthanum at the A site is an alkaline oxide, and the catalytic activity as a catalyst for a dehydrogenation reaction at a relatively low temperature of 650° C. is improved.
[0226] In addition, in samples C1 to C4 among samples C1 to C8, part of the strontium or barium at the A site is replaced by lanthanum. As a result, in samples C1 to C4, the basicity and oxygen deficiency amount as catalysts for dehydrogenation reactions increase. In the methane oxidative coupling reaction at high temperatures above 700°C, the movement of CO2 molecules generated as byproducts during the methane oxidative coupling reaction is activated. Therefore, regardless of the type of material, it is not easily affected by the adsorption of CO2 molecules. Composite oxides containing strontium or barium are useful as catalysts in the methane oxidative coupling reaction. However, at low temperatures below 700°C, such as 650°C, for example, strontium and barium, which are alkaline earth metals, are elements that easily form carbonates. Therefore, there is a concern that CO2 molecules, which are byproducts of the methane oxidative coupling reaction, may be adsorbed and cause catalyst poisoning that is easily deactivated. On the other hand, as in samples C1 to C4, by replacing part of the strontium or barium at the A site with lanthanum, which is less likely to form carbonates, the catalyst for the dehydrogenation reaction is less likely to form carbonates than the composite oxide containing strontium or barium. It is believed that the effect of the adsorption of CO2 molecules at 650°C is reduced, making it less likely to be deactivated.
[0227] Furthermore, as shown in sample C11, it is shown that when lanthanum is introduced into SrTiO3, the catalytic activity as a catalyst for dehydrogenation reaction decreases. It is thus confirmed that the amount of lanthanum added, which is required to improve the catalytic activity without being affected by the adsorption of CO2 molecules, is insufficient when it is a trace amount. When the amount of lanthanum added is a trace amount, the effect of lanthanum's lower basicity than strontium becomes advantageous, and it is believed that the catalytic activity decreases. In this way, in order to reflect the effect that lanthanum is not easy to cause the adsorption of CO2 molecules, the amount of lanthanum added must be large.
[0228] In addition, as in sample C11, it is believed that when the B site is a tetravalent element, the amount of lanthanum substitution becomes insufficient. Therefore, as in samples C1 to C8, the dehydrogenation reaction catalyst of the perovskite-type oxide having a trivalent element at the B site and lanthanum introduced into the A site is superior to the dehydrogenation reaction catalyst of the perovskite-type oxide having a tetravalent B site such as sample C11. It can be said that the methane oxidative coupling reaction is excellent. In addition, it was confirmed that sample C3, in which the amount of lanthanum substitution at the A site is 0.6, exhibits an excellent methane oxidative coupling reaction as a dehydrogenation reaction catalyst. Thus, by making the amount of lanthanum substitution at the A site at least 0.4 or more, the dehydrogenation reaction catalyst can exhibit an excellent methane oxidative coupling reaction.
[0229] According to the dehydrogenation reaction catalyst of the present embodiment having the above configuration, the perovskite-type oxide containing lanthanum in the A site is provided. Thus, the catalytic activity of the dehydrogenation reaction catalyst, which promotes the dehydrogenation reaction at a low temperature, can be improved.
[0230] In addition, according to the dehydrogenation reaction catalyst of the present embodiment, lanthanum and strontium or barium are simultaneously contained at the A site. This can further improve the catalytic activity of the dehydrogenation reaction catalyst, and the catalytic activity of promoting the dehydrogenation reaction at a relatively low temperature.
[0231] Furthermore, according to the catalyst for dehydrogenation reaction of the present embodiment, when used as a methane oxidative coupling catalyst, the catalytic activity of the methane oxidative coupling catalyst at low temperature can be improved.
[0232] <Modification of this embodiment>
[0233] The present invention is not limited to the above-described embodiment, and can be implemented in various forms without departing from the gist of the invention. For example, the following modifications are possible.
[0234] [Modification 1]
[0235] In the first embodiment, for the spectrum of the O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy, the catalyst for dehydrogenation reaction having a ratio of the second peak area to the first peak area greater than 1 is a composite oxide having a main phase having a perovskite-type oxide crystal structure represented by formula (1) and a secondary phase having at least one of the three composite oxides represented by formulas (2a) to (2c). However, the configuration of the catalyst for dehydrogenation reaction having a ratio of the second peak area to the first peak area greater than 1 is not limited thereto.
[0236] The present disclosure is not limited to the above-mentioned embodiments, etc., and can be implemented in various configurations within the scope of the main purpose. For example, in order to solve part or all of the above-mentioned problems, or to achieve part or all of the above-mentioned effects, the technical features in the embodiments corresponding to the technical features in the various modes recorded in the column of the invention content can be appropriately replaced or combined. In addition, if the technical features are not described as necessary in this specification, they can be appropriately deleted.
[0237] The present disclosure can also be implemented in the following forms.
[0238] [Application Example 1]
[0239] A catalyst for dehydrogenation reaction, characterized in that it comprises:
[0240] The main phase is composed of the general formula (A 1-x A' x )(Zr 1-y-z B y B' z ) 3-δ (wherein A is at least one element selected from alkaline earth metals, A' is at least one element selected from lanthanum (La) and yttrium (Y), B is at least one element selected from titanium (Ti) and cerium (Ce), B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and neodymium (Nd), and 0≤x≤0.4, 0.3≤(1-z)≤1, 0≤y, 0<(1-yz), and δ represents an oxygen deficiency amount) is composed of a perovskite-type oxide; and,
[0241] The subphase is composed of at least one of three composite oxides represented by the general formula AB'2O4, A2B'2O5, and A3B'4O9 (wherein A and B' are elements common to A and B' constituting the above-mentioned perovskite-type oxide).
[0242] [Application Example 2]
[0243] The catalyst for dehydrogenation reaction according to Application Example 1 is characterized in that:
[0244] The aforementioned A is barium (Ba),
[0245] The aforementioned B' is scandium (Sc),
[0246] The subphase is composed of barium scandate (at least one of the three composite oxides of BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9).
[0247] [Application Example 3]
[0248] The catalyst for dehydrogenation reaction according to Application Example 1 or Application Example 2 is characterized in that:
[0249] The aforementioned subphase is composed of Ba3Sc4O9.
[0250] [Application Example 4]
[0251] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 3 is characterized in that
[0252] The aforementioned main phase is composed of BaZr 1-z Sc z O 3-δ (where 0.1≤z≤0.7).
[0253] [Application Example 5]
[0254] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 4 is characterized in that
[0255] In the powder X-ray diffraction spectrum using CuKα radiation,
[0256] The perovskite-type oxide constituting the main phase has a first peak with the highest peak intensity in the range of diffraction angle 2θ=29.5-30.5°, and the composite oxide constituting the subphase has a second peak with the highest peak intensity in the range of diffraction angle 2θ=30.6-31.0°,
[0257] The ratio of the intensity of the second peak to the intensity of the first peak is 0.04 or more.
[0258] [Application Example 6]
[0259] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 5 is characterized in that
[0260] The subphase is composed of any one of the three types of composite oxides.
[0261] [Application Example 7]
[0262] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 6 is characterized in that
[0263] This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
[0264] [Application Example 8]
[0265] A catalyst for dehydrogenation reaction, characterized in that:
[0266] Regarding the spectrum of O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy,
[0267] The first curve has a first peak corresponding to a local maximum value in the range of 525-530 eV for the bonding energy, and the second curve has a second peak corresponding to a local maximum value in the range of 530-535 eV for the bonding energy by peak separation fitting processing.
[0268] When the area of the convex portion including the first peak in the first curve is defined as the first peak area, and the area of the convex portion including the second peak in the second curve is defined as the second peak area,
[0269] The ratio of the second peak area to the first peak area is greater than 1.
[0270] [Application Example 9]
[0271] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 8 is characterized in that
[0272] Has oxygen deficiency.
[0273] [Application Example 10]
[0274] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 9 is characterized in that
[0275] The main phase of the above-mentioned catalyst is a perovskite structure.
[0276] [Application Example 11]
[0277] The dehydrogenation reaction catalyst according to any one of Application Examples 1 to 10 is characterized in that
[0278] The specific surface area measured by the BET method is 10m 2 / g or above.
[0279] [Application Example 12]
[0280] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 11 is characterized in that
[0281] This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
[0282] [Application Example 13]
[0283] A catalyst for dehydrogenation reaction, characterized in that:
[0284] Its general formula (La 1-x M1 x )M2O 3-δ(wherein, M1 is at least one element selected from alkaline earth metals, M2 is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and gallium (Ga), and δ represents the amount of oxygen deficiency, satisfying 0≤x≤0.6) as shown in the perovskite structure.
[0285] [Application Example 14]
[0286] The dehydrogenation reaction catalyst according to any one of Application Examples 1 to 13 is characterized in that
[0287] The aforementioned M1 is strontium (Sr) or barium (Ba).
[0288] [Application Example 15]
[0289] The catalyst for dehydrogenation reaction according to any one of Application Examples 1 to 14 is characterized in that
[0290] This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
Claims
1. A catalyst for dehydrogenation reaction, characterized in that: have: The main phase is composed of the general formula (A 1-x A' x )(Zr 1-y-z B y B' z ) 3-δ The perovskite-type oxide shown in the figure is composed of, wherein A is at least one element selected from alkaline earth metals, A' is at least one element selected from lanthanum (La) and yttrium (Y), B is at least one element selected from titanium (Ti) and cerium (Ce), B' is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and neodymium (Nd), satisfying 0≤x≤0.4, 0.3≤(1-z)≤1, 0≤y, 0<(1-yz), and δ represents the amount of oxygen deficiency; and, The subphase is composed of at least one of three composite oxides represented by the general formula AB'2O4, A2B'2O5, and A3B'4O9, wherein A and B' are elements common to A and B' constituting the perovskite-type oxide.
2. The catalyst for dehydrogenation reaction according to claim 1, characterized in that A is barium (Ba), The B' is scandium (Sc), The subphase is composed of barium scandate, and the barium scandate is at least one of three composite oxides: BaSc2O4, Ba2Sc2O5, and Ba3Sc4O9.
3. The catalyst for dehydrogenation reaction according to claim 2, characterized in that The subphase is composed of Ba3Sc4O9.
4. The catalyst for dehydrogenation reaction according to claim 3, characterized in that The main phase is composed of BaZr 1-z Sc z O 3-δ Composition, wherein 0.1≤z≤0.
7.
5. The catalyst for dehydrogenation reaction according to claim 4, characterized in that In the powder X-ray diffraction spectrum using CuKα radiation, The perovskite-type oxide constituting the main phase has a first peak with the highest peak intensity within the range of a diffraction angle of 2θ=29.5-30.5°, and the composite oxide constituting the subphase has a second peak with the highest peak intensity within the range of a diffraction angle of 2θ=30.6-31.0°, The ratio of the intensity of the second peak to the intensity of the first peak is 0.04 or more.
6. The catalyst for dehydrogenation reaction according to claim 1 or claim 2, characterized in that: The subphase is composed of any one of the three composite oxides.
7. The catalyst for dehydrogenation reaction according to claim 1 or claim 2, characterized in that: This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
8. A catalyst for dehydrogenation reaction, characterized in that: Regarding the spectrum of O1s orbital contained in the photoelectron spectrum obtained by X-ray photoelectron spectroscopy, The first curve has a first peak corresponding to a local maximum value in the range of 525-530 eV for the bonding energy, and the second curve has a second peak corresponding to a local maximum value in the range of 530-535 eV for the bonding energy by peak separation fitting processing. When the area of the convex portion including the first peak in the first curve is defined as the first peak area, and the area of the convex portion including the second peak in the second curve is defined as the second peak area, The ratio of the second peak area to the first peak area is greater than 1.
9. The catalyst for dehydrogenation reaction according to claim 8, characterized in that Has oxygen deficiency.
10. The catalyst for dehydrogenation reaction according to claim 8 or claim 9, characterized in that: The main phase of the catalyst is a perovskite structure.
11. The catalyst for dehydrogenation reaction according to claim 8 or claim 9, characterized in that: The specific surface area measured by the BET method is 10m 2 / g or above.
12. The catalyst for dehydrogenation reaction according to claim 8 or claim 9, characterized in that: This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
13. A catalyst for dehydrogenation reaction, characterized in that: Its general formula (La 1-x M1 x )M2O 3-δ The perovskite structure shown, wherein M1 is at least one element selected from alkaline earth metals, M2 is at least one element selected from yttrium (Y), scandium (Sc), ytterbium (Yb), aluminum (Al), indium (In), and gallium (Ga), and δ represents the amount of oxygen deficiency, satisfying 0≤x≤0.
6.
14. The catalyst for dehydrogenation reaction according to claim 13, characterized in that The M1 is strontium (Sr) or barium (Ba).
15. The catalyst for dehydrogenation reaction according to claim 13 or claim 14, characterized in that: This is a methane oxidative coupling catalyst for producing hydrocarbons having 2 or more carbon atoms from methane.
Citation Information
Patent Citations
Methane oxidation conversion
JP1986282323A
Production of alkali metal halide-supporting samarium oxide catalyst
JP1996010620A